Exogenous phytohormone-assisted rotating algal biofilm reactor for enhanced polyacrylamide wastewater treatment and bioresource recovery - Huichao Zhang; Wuzhou Luo; Tianhao Wu; Zhongyi An; Jingwen Xu; Wenyunxi Shan; Dan Li (Bioresource Technology, 2026)

Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Effects of two enzyme–microbe co-fermented feed formulations on growth performance, ruminal fermentation, serum metabolome, and gastrointestinal microbiota in mid-fattening simmental heifers - Keren Yang; Ting Liu; Hanfang Zeng; Zhenling Wu; Xuanwei Lv; Daiwei Li; Zhiwen Xu; Liming Wei; Dehai An; Shicheng Wang; Chen Zheng (Animal Feed Science and Technology, 2026)

Cratonic reworking and basin-system differentiation: from a shared upper paleozoic coal-measure foundation to contrasting gas systems in North China - Weikai Xu; Yong Li; Xiao-Fang He; Yiwen Ju; Thomas J. Algeo; Xiaokang An (Earth-Science Reviews, 2026)

Mesoporous-nanoreactor-confined PtRuNiCoCu high-entropy alloy nanoparticles for superior alkaline hydrogen oxidation reaction - Lianming Zhao; Jinghao Zhang; Chang Xu; Shouao Li; Yanfu Tong; Guangkun Yan; Wenxuan An; Pengyun Liu; Xuejin Li; Guang Zhao; Jing Xu; Wei Xing (Chemical Engineering Journal, 2026)

A chiral metal-organic cage Al-CMOC for high-resolution gas chromatographic separation - Xiao-Fang Shu; An-Xu Ma; Fu Li; Chang-Xiu Ma; Jin Liu; Xu-Xu Jin; Sheng-Ming Xie; Bang-Jin Wang; Jia-Ni Yang; Jun-Hui Zhang; Li-Ming Yuan (Analytica Chimica Acta, 2026)

Grazing intensity regulates short-term responses of soil moisture, plant community and carbon exchange to rainfall pulses in a desert steppe - Xu Li; Xiaolong Chen; Wenling Fu; Chunchun An; Xiaoqian Li; Tianming Gao; Xinchuang Chen; Huaichang Wang; Jianying Guo; Zhi Dong (Agriculture, Ecosystems & Environment, 2026)

The overlooked risk of activated peroxymonosulfate: Significant free chlorine and volatile disinfection byproduct formation - Renyuan Zhang; Wenjun Xu; Zishi An; Genye He; Yue Lu; Jing Li (Water Research, 2026)

Integrated strategy for genistein production from soybean meal: Microbial mining, enzymatic mechanism, and temperature-adaptable solid-state fermentation - Hang Xu; Li-Ming Luo; Hao-Nan Cao; Hao An; Jian-Gong Duan; Yong-Xing He; Hao Yang (Journal of Environmental Chemical Engineering, 2026)

Prediction toxicity threshold of herbicides single and combine to submerged plants: A QSAR model with ridge regression - Min Hu; Gujie Zhu; Zepeng Zhang; Yangyang Zhang; Xu Huang; Shuqing An; Aimin Li (Journal of Environmental Chemical Engineering, 2026)

Enhancing CO2 capture capacity and selectivity in UTSA-16(Co) via elevated-temperature synthesis for flue gas separation - Ranjit Gaikwad; Sunita Gaikwad; Jiayi Li; Hiluf T. Fissaha; Radhakrishnan Anbarasan; Hua An; Le Xu; Shipeng Ding; Qiang Wang (Journal of Environmental Chemical Engineering, 2026)

Revealing the dominant role of pectin in softening texture and enhancing drying behaviors of grapes after cold plasma pretreatment - An-An Zhang; Fan Yang; Ming-Qiang Xu; Wei-Peng Zhang; Jin-Run Li; Hai-Bin Yang; Jing-Shou Zhang; Wei-Qiao Lv; Hong-Wei Xiao (Food Research International, 2026)

Effects of rolling temperature on green tea flavor from integrated metabolomics and flavor quantification - Xinxin Xu; Jinjin Wang; Lichi Qu; Ranyang Li; Yongwen Jiang; Jinjie Hua; Ting An; Hao Zheng; Kunbo Wang; Haibo Yuan (Food Research International, 2026)

Metal-organic frameworks nanozyme-integrated portable microneedle patch for visual bacterial monitoring in meat - Jiayu Cheng; Heng An; Xiangdan Meng; Li-Ping Xu (Food Chemistry, 2026)

Three-dimensional printed zerovalent iron enables selective and sustained reductive dehalogenation of florfenicol via structure-induced corrosion resistance and electron transfer regulation - Dan Li; Lu Liu; Haochen Li; Tao Ye; Junhong Wu; Jiaying Li; Si Zhai; Mengli Li; Huigai Wei; Lei Li; Jianhui Xu; Peng Liu; et al. (Environmental Research, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

A physics-guided neural surrogate framework for bridge weigh-in-motion based on influence-line superposition - Jian-An Li; Yan Zeng; Dongming Feng; Baoquan Wang; Yichao Xu (Engineering Structures, 2026)

Corrigendum to “flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction” [Chem. Eng. J. 521 (2025) 166451] - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2026)

Ambient-air fabrication of high-performance thick-film organic solar cells enabled by solid additive engineering - Kun Li; Cunbin An; Yuan Yao; Jianbin Zhong; Bin Hu; Wei Zhang; Yishi Wu; Bowei Xu; Dianyi Liu; Guanghao Lu; Qing Liao; Xiaozhang Zhu; et al. (Chemical Engineering Journal, 2026)

A honeycomb film containing self-assembling microgels for long-term live microbiota preservation - Yudi Shen; Fupei Xu; Tingtao An; Yueru Li; Jingmin Liu; Jing Wu; Shuo Wang (Chemical Engineering Journal, 2026)

Recent advances in membrane materials for efficient xylene isomers separation - Yating Zhu; Yinghui Xu; Fengkai Wang; Jie Li; Naixin Wang; Quan-Fu An (Chemical Engineering Journal, 2026)

Determination of NO2 emission rates from residential gas stoves with continuous indoor monitoring - Xinchen Le; Jianwei Gu; Xu Du; Qiaoqiao Wang; Xiaoliang Qin; Zhi Ning; Ming Zhou; Guiying Li; Taicheng An (Atmospheric Environment, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

Under greenhouse settings, mycorrhizal responsive herbs establish better in their own soil compared to less responsive counterparts - Stavros D. Veresoglou; Yang Liu; Jie Bai; Hanzhi Bao; Peipei Bao; Bolun Cai; Liqun Cai; Jiawei Cao; Chen Chen; Genrun Chen; Hongqiao Chen; Jiarong Chen; et al. (Plant and Soil, 2026)

Natural IgM induced by chitosan oligosaccharide confers resistance to GCRV-II in grass carp - Yan-Hui Huang; Bin Liu; Wen-Jing Dong; Yong Liu; Nan Zhang; Jie Li; Yong-An Zhang; Xu-Jie Zhang (Aquaculture, 2026)

Mass-compensated implantable accelerometery for harvest-induced walnut (Juglans regia L.) dynamics - Jianshuo An; Jiale Cao; Heng Chen; Wei Zhu; Daochun Xu; Xiaopeng Bai; Wenbin Li (Biosystems Engineering, 2026)

Factors underlying early cross-protection elicited by a lineage 1 branch porcine reproductive and respiratory syndrome virus live vaccine candidate - Chao Li; Jinhao Li; Bangjun Gong; Jiahao Shi; Xueli Zhang; Zhenyang Guo; Lirun Xiang; Siyu Zhang; Zixuan Feng; Haonan Kang; Yan-Dong Tang; Kuan Zhao; et al. (Veterinary Microbiology, 2026)

Mechanism for reduction swelling of basic oxidized pellets: A perspective based on phase evolution - Xingwang Li; Yuan Zuo; Chao Xu; Jingshu An; Yifan Wang; Jie Lei; Hongming Long (Minerals Engineering, 2026)

Zn-La staged modification of reed biochar for adsorption of tetracycline hydrochloride and mechanism study - Zhengqi Liang; Xiongyan Gao; Yushan Li; Xu Liu; Boxing An; Yingying Zuo; Ling Wang; Jiahui Fu; Meili E (Journal of Water Process Engineering, 2026)

Biotransformation of Cimetidine by Chlamydomonas sp. SI-16: CYP450-Driven Detoxification and Immobilized Photobioreactor Validation - Kang Li; Jun Liu; Yongtao Cheng; Chenxi Zhou; Kang Shan; Chuanyue Peng; Wenjing Yan; Ying Liu; An Xu; Min Zuo (Journal of Hazardous Materials, 2026)

Exposure of dairy goat mammary epithelial cells to bis(2-ethylhexyl) phthalate induces oxidative stress and alters gene/protein expression, posing health risks - Xiaolong Xu; Muhua Luo; Jiaxiang Hu; Haifeng Wang; Xugan Wang; Jiaqi Bu; Jiayuan Li; Hanbing Yan; Xiaopeng An (Journal of Environmental Sciences, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

Antibiotic resistance genes (ARGs) in rice: Source attribution and putative mobility patterns - Jie Hou; Ye Li; Mengqi Liu; Linyun Li; Hongan Chen; Yi An; Han Xu; Yanpo Yao (Food Microbiology, 2026)

High-efficiency capacitive deionization enabled by spin-state modulation of iron centers in Fe5C2/Fe3O4 heterostructures - Jiacen An; Dawei Chu; Xueying Xu; Guang Xu; Dong-Feng Chai; Dantong Zhang; Guozhe Sui; Jinlong Li; Dongxuan Guo (Chemical Engineering Journal, 2026)

Carboxyl-group-guided ultrafast potassium wetting for long-cycling potassium metal batteries - Jinyuan Chen; Changyuan Guo; Qinyou An; Wei Li; Xiaoming Xu; Jianwei Li; Xinjie Wang; Daohang Fu; Chunhua Han; Chaojiang Niu; Xuanpeng Wang (Chemical Engineering Journal, 2026)

Atmospheric pressure drying method for constructing thermal insulation cellulose aerogels with excellent flame retardancy - Xinyu An; Chang Ma; Xu Li; Zhiming Liu (Chemical Engineering Journal, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Exogenous Organic Acid–Induced Reconfiguration of Extracellular Polymeric Substances Enhances Biological Nitrogen Removal - Chuchu Wang; Ao Xu; Shangbin Ma; Dawen Gao; Xiaofei Gong; Tiantian Li; Zheng Huang; Yanyu An (Water, Air, & Soil Pollution, 2026)

Effects of Euryale ferox seed shell on the growth, antioxidant capacity, and immune function of yellow catfish (Pelteobagrus fulvidraco) - Jiayue Zeng; Guowei Liao; Zicong Li; Wei Li; Zhaojia Zhao; Haonan Xu; Bing Wang; Xinpeng Zhang; Meitong Zhang; Junqi An; Fang Zeng (Animal Feed Science and Technology, 2026)

A comparative study on the accuracy of SWOT satellite river water level retrieval using different matching methods: a case study of the Yangtze River Basin - Zeyu Chen; Peng Chen; Yang Chen; Hang Liu; Zheng Li; Zhiyuan An; Zufeng Li; Xin Xu; Yibin Yao (Advances in Space Research, 2026)

YRD1km: A 1-km Hourly High-Resolution Regional Reanalysis Dataset over the Yangtze River Delta with Emphasis on Thermodynamic Structure - Yan-An Liu; Zhengyan Zhang; Tianyue Zeng; Zhenglong Li; Pengbo Xu; Juan Zhang; Bo Li; Jun Li (Advances in Atmospheric Sciences, 2026)
High-resolution atmospheric thermodynamic information is essential for resolving localized weather processes in complex urbanized regions such as the Yangtze River Delta (YRD). However, existing global reanalysis products are limited by coarse spatial resolution, constraining their ability to represent fine-scale thermodynamic structures. In this study, we develop YRD1km, a 1-km hourly regional thermodynamic reanalysis dataset for the YRD, generated through dynamical downscaling of ERA5 using the WRF model with a three-level nested configuration. The framework integrates optimized physical parameterizations, a combined observation and analysis nudging strategy, and updated high-resolution land-use information. The current dataset covers the summer seasons (June–August) from 2021 to 2023, a period characterized by frequent convection and strong land–atmosphere interactions. Comprehensive validation against dense surface and radiosonde observations demonstrates that YRD1km consistently outperforms ERA5 in near-surface temperature, relative humidity, and surface pressure, with reductions of approximately 35% in MAE and RMSE for temperature and humidity and more than 78% for surface pressure. Vertical evaluations reveal substantial improvements throughout the troposphere, particularly for moisture fields. YRD1km also exhibits enhanced temporal stability and reduced discontinuities associated with assimilation window transitions in ERA5. A severe convective case further illustrates its ability to resolve multi-level thermodynamic anomalies preceding convective initiation. Overall, YRD1km provides a physically consistent, high-resolution thermodynamic reanalysis framework that supports detailed weather diagnostics, urban meteorology studies, and future regional AI-based weather modeling applications.

Root exudates as molecular architects redefining carbon footprint of nitrogen-cycling in constructed wetlands: From ecological responses to application perspectives - Xiaofei Gong; Yanyu An; Tiantian Li; Ao Xu; Zheng Huang; Chuchu Wang; Yuqiu Liu; Dawen Gao (Critical Reviews in Environmental Science and Technology, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Precise nanodelivery of screened compounds alleviates sepsis-associated encephalopathy by targeting microglial ANXA2 - Daoyi Lin; Yuan Huang; Shuyan Wu; Zefu Li; Hanhao Dai; Fei Gao; Danfeng Wang; Maokai Xu; Ziqi An; Xinmu Li; Peng Ye; Yingjie Chen; et al. (Science Bulletin, 2026)

Seasonal variation of fish biodiversity in Xisha Islands based on dual-marker eDNA metabarcoding - Shengming Deng; Yuguo Ye; Min Liu; Bai-an Lin; Chengdan Ma; Yifeng Xu; Yongcan Zhou; Shifeng Wang; Weiliang Guo; Huilong Ou; Xiang Zhang; Jianlong Li (Marine Environmental Research, 2026)

Magnetotactic bacteria antagonized lead toxicity: Distinct detoxification mechanisms in magnetosome-containing/deficient bacteria - Ruoyun Dong; Yuting Ding; Han Li; Yanan Zhao; Yuanyuan Wu; Chenxi Zhou; An Xu; Yun Liu (Journal of Environmental Sciences, 2026)

Pulsed electric field processing of buffalo milk with retained Joule heating: Microbial efficacy, bioactive protein retention, and flavor profiling - Lang-Hong Wang; Jia-Hong Li; Xu-Rui Li; Yu-Xi Hu; Rui Wang; Xin-An Zeng (Innovative Food Science & Emerging Technologies, 2026)

Two stages of Sn enrichment in granitic magmatism: insights from Sn isotopes of cogenetic minerals - Jia-Xin She; Weiqiang Li; Ru-Cheng Wang; Lei Xie; Chen Liu; Zhihao Xu; Shichao An; Cheng Xu (Geochimica et Cosmochimica Acta, 2026)

Engineering an amino-modified MOF@COF interface to construct a light-responsive oxidase-like nanozyme for rapid total antioxidant capacity assay in foods - Yanhui Feng; An Xu; Huan Li; Xiumei Lin; Hongxu Guo (Food Chemistry, 2026)

Comprehensive study on the interaction of estrogen and Microcystis aeruginosa with coexisting of microplastics - Xin Xu; Jiale Li; Lili An; Wenyu Zhao; Ruihua Dai (Environmental Pollution, 2026)

The effect of arbuscular mycorrhizal fungi on the physiological and biochemical functioning of the ornamental species Catalpa bungei against Meloidogyne incognita - Zhen-Hui Wang; Xue-Li Mou; Pan-Pan Meng; Gui-Hua Meng; Wei Chen; Xia-An Tang; Ke-Xu Xin; Yi Zhang; Chun-Yan Wang (European Journal of Plant Pathology, 2026)

Mountain river response to a large input of sediment: a long-term geometric record of the Lillooet River (1947–2022) - Wenqi Li; Liuying An; Quanxi Xu; Kejun Yang; Zhongwu Jin; Qihang Zhou; Hongsheng Fu (Environmental Fluid Mechanics, 2026)

CARE Radiative Transfer Model: A Tool for Supporting Polarization and Hyperspectral Radiative Transfer Simulation in the Coupled Atmosphere–Ocean System - Chong Shi; Husi Letu; Teruyuki Nakajima; Miho Sekiguchi; Wenwu Wang; Ruijie Yao; Huazhe Shang; Shuai Yin; Jian Xu; Ni An; Wenke Jiang; Yuxiang Cui; et al. (Advances in Atmospheric Sciences, 2026)

Expression of Transforming Growth Factor Beta 1 in Lung Adenocarcinoma and Its Relationship with Circulating Tumour Cells - Ning Chen; Duo-Jun Qiu; Jian-Zhu Yang; Gui-Yun Zhu; Li-Fei Kang; Xiao-Ying An; Zhi-Ming Xu; Xiao-Xia Li (Biochemical Genetics, 2026)

Occurrence and potential sources of greenhouse gases at Wuzhen, a typical ancient water town in Eastern China - Zheng Xia; Jiasi Shen; Peipei Shao; Wenlong Zhao; Bingye Xu; Xudong Tian; Yang Wu; Changlin Zhan; Saiya An; Nan Li; Zhengning Xu; Bo Yao; et al. (Environmental Monitoring and Assessment, 2026)

Accelerating the discovery of high-performance MOFs for N2 capture via fALIGNN: Bridging physical pore descriptors and atomic structures - An Li; Xin Xu; Shaoxuan Huang; Maogang He; Xiangyang Liu (Process Safety and Environmental Protection, 2026)

Nitrogen limitation enhances Irgarol 1051 toxicity by aggravating PSII photoinhibition in the marine diatom Thalassiosira weissflogii - Yuheng An; Shumin Zeng; Futian Li; Jun Wang; Xuexia Zhu; Juntian Xu; Yaping Wu (Marine Environmental Research, 2026)

Stable cerium isotopic fractionation during alkaline magma differentiation and the isotopic composition of the upper continental crust - Fang Liu; Xin Li; Yajun An; Jianbing Xu; Mingxing Ling; Yu Yuan; Zhaofeng Zhang (Geochimica et Cosmochimica Acta, 2026)

Transforming a protease inhibitor into a peptide Guardian: BBI-armed hydrogel beads for Oral delivery of active peptides - Qiaolian Xu; Wanru Li; Jiulong An; Jian Li; Xinqi Liu; He Li (Food Research International, 2026)

Advanced engineered materials for emerging contaminant remediation toward water treatment - Xinyu Wang; Haoyang Wang; Xiaobin Yang; Xu Wang; Yangxue Li; Xiangli Meng; Bhekie B. Mamba; Alicia Kyoungjin An; Lu Shao (Chemical Engineering Journal, 2026)

Construction dual-temperature responsive hydrogel of hydroxypropyl methylcellulose and κ-carrageenan via formation of dynamic semi-interpenetrating physical structure - Mengya Sun; Qiongyu Wang; Jiulong An; Qiaolian Xu; He Li; Xinqi Liu; David Julian McClements; Yating Huang; Zhihua Pang (Carbohydrate Polymers, 2026)

Mechanistic insights into glufosinate-ammonium (GLA)-Induced brain injury revealed by LC-MS/MS-based metabolomics - Huan-le Ye; Xin-xin Zheng; Mian-mian Li; Zhi-qiang Zhang; Liu-xu Chen; Wen-jing Zhang; Ren Cheng-Han Fan; Guo-xin He; An-cong Xu (Chemico-Biological Interactions, 2026)

BaP and 17β-estradiol affect retromer-VPS35, restricting pro-survival transcription and exacerbating neurotoxicity in a reclaimed water environment - Liang Xu; Chuanbing Wu; Yu Xia; Mengyuan An; Peng Wang; Wansheng Zhang; Wenwen Li; Yuhan Zhou; Junkai Hao; Dazhi Sun; Zhipeng Zhang; Caiyun Sun (Aquatic Toxicology, 2026)

Breaking the sensitivity barrier in ELISA: A molecularly engineered peptide nanointerface achieves ultrasensitive detection of zearalenone - Zijun Yang; Zhiwei Liu; Zhongqi Lin; Wenjuan Xu; Xiu'an Duan; Zhenlin Xu; Xiangmei Li (Analytica Chimica Acta, 2026)

Experiments of orthometric height determination by transportable clock referred to GNSS time - Lei Wang; Lihong Li; Pengfei Zhang; Wei Xu; An Ning; Rui Xu; Ziyu Shen; Kuangchao Wu; Wenbin Shen (Advances in Space Research, 2026)

Molecular characterization and whole-genome sequencing-based genetic evolution of coxsackievirus A16 in Taiyuan City, 2023–2025 - Yanqin Wang; Jihong Xu; Lifeng Zhao; Yunyun Li; Yang Xu; Ruihong Gao; Xiaofang Guo; Min Niu; Zhihong Zuo; Teng An; Jitao Wang (Archives of Virology, 2026)

Lactobacillus johnsonii DM2420 Alleviates Dyslipidemia, Remodels Gut Microbiota, and Modulates the Intestinal CD36/SREBP1 Signaling Axis - Jiaxin An; Qianrui Wei; Yafang Xu; Yinghan Xiang; Zhouyi Wang; Bing Wang; Huajun Li (Probiotics and Antimicrobial Proteins, 2026)

A new perspective on real-time monitoring and function interpretation of nitrification based on machine learning and mass-to-charge fingerprint - Chen-Shun Lu; Shilong He; Chunmiao Wang; Jiaxun Guo; Yunzhi Qian; Yonghao Zhu; Xiaoliang Fan; Jiayao Ding; Shen Han; Chao Li; An Xu; Bo Nie; et al. (Water Research, 2026)

Acute exercise activates hepatic Nrf2 signaling by ROS, AMPK and epinephrine to protect against acute liver injuries - Simin Yang; Ranting Zhao; Li Lei; Xiangbo An; Jiangli Xu; Han Xu; Jiahui Wang; Han Xiao; Youyi Zhang; Xiaoda Yang; Siwang Yu (Toxicology and Applied Pharmacology, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

In-situ engineered RuTiOx nanorods for synergistic AEM-LOM pathways enabling overall water splitting - Bei An; Huijie He; Tianwen Chen; Ziran Xu; Xiaozhe Liu; Xiaoxiao Zeng; Xiaoqian Li; Meijing Cao; Fanfan Shang; Xiaojing Yu; Miao Song; Bingbao Mei; et al. (Science Bulletin, 2026)

Assessing humus to predict soil organic carbon in Northwest China: A case study of Ningxia - Xinnian GUO; Zhuonan HOU; Xia WU; Huaiyu LONG; Zehua XU; Baiyun LI; Shaoshan AN (Pedosphere, 2026)

Dual repression of OsSnRK1β1A by the deubiquitinase OsOTUB1 orchestrates energy metabolism and grain yield in rice - Ludan Zhang; Pengfei Wang; Yue Li; Shuang Yang; Yan Chen; Zhiying Ma; Jing Pan; Xiaoyu Wang; Chenyan Wang; Haoyuan An; Yuqing Xu; Yifei Xiao; et al. (Molecular Plant, 2026)

Mechanism-based assessment of respirable dust exposure in miners: Integrating CFD-DPM simulation with personalized monitoring for occupational health risk - Jiajun An; Fan Geng; Yuqing Feng; Changgeng Gui; Shihang Li; Xinjian He; Guang Xu; Zheng Zhang; Yibao Wang (Journal of Environmental Chemical Engineering, 2026)

Exogenous phytohormone co-application enhances polyacrylamide removal and microalgal-bacterial biofilm development in a revolving algal biofilm reactor - Zhongyi An; Renrunbang Li; Tianhao Wu; Huichao Zhang; Jingwen Xu; Qingbin Zhao; Dongrun Sui; Dan Li (Journal of Environmental Chemical Engineering, 2026)

Engineering directed charge transport pathway in MOF@COF hetero-framework for enhanced singlet oxygen production and tetracycline photo-oxidation - Xiaorui Du; Lifei Liu; Pengfei Li; Luyuan Zhang; Yang Deng; Xia An; Xu Wu (Journal of Environmental Chemical Engineering, 2026)

From structure to reactivity: Radical-mediated dehydrogenation of tetralin by exinite and vitrinite in a Xinjiang coal - Siyu Wang; Jiani Peng; Wang Li; Zizhen Xu; Liang An; Qingya Liu; Zhenyu Liu; Yuxin Yan; Sasha Yang; Lei Shi (Fuel, 2026)

Accurate geographical origin identification of winter jujube PGIs by mineral elements and stable isotopes in flesh and pit - Mengying Shuai; Zhichao Li; Xiabing Kong; An Li; Qiusheng Chen; Duoyong Zhao; Min Xu; Mengyao Yang; Kangni Yang; Jiyun Nie (Food Chemistry, 2026)

Structure–function relationships in chitosan films containing ZIF-8-confined Ligusticum jeholense essential oil: pH-triggered release and apple ring rot control - Xiao-Yi Tong; Yun-Feng Liu; Zhi-Hong Xu; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An; Fei Cao (Food Chemistry, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

Efficient production of high-performance thermally conductive adhesives by in situ one-pot liquid-phase exfoliation approach - Tonghao Zhu; Sha Wang; Chen Chen; Jiaying Mo; Huijian Ye; Weili Yan; Yufei Li; Mingxing An; Lixin Xu (Chemical Engineering Journal, 2026)

From energy-limited to substrate-limited: Machine learning reveals the spatially shifting controls on cirque morphology in high Mountain Asia - Jinrong Hu; Fuyuan An; Li Yan; Hongjun Yu; Longfei Gai; Xue Min; Ruiyang Xu (CATENA, 2026)

The autophagy-related protein OsCOST1 negatively regulates the salt tolerance in rice - Xiaole Fan; Zimeng Pan; Xiaotong Xu; An Yan; Bei Li; Ying Zhao; Xiaotong Guo; Chunyan Yu; Hongxia Zhang (Plant Cell Reports, 2026)

Impact of land use transition on ecosystem services in the Yangtze River economic belt and associated mechanism - Youzhi An; Mengsha Fan; Zhihao Tao; Peng Zhao; Hualin Chen; Da Li; Yun Wu; Qiuju Wu; Jin Sun; Feng Xu; Fengtai Zhang (Environment, Development and Sustainability, 2026)

Structural controlling conditions for dry hot rock reservoirs in the middle section of the northern margin in the North China Block - Yan-Xu Liu; Wen-Yong Li; Shan-Gao; An-Qi Cao; Zhe-Xin Jiang; Wei-di Meng (Applied Geophysics, 2026)

Characterization, expression, and functional analysis of sarcospan (SSPN) in Chinese tongue sole: Cynoglossus semilaevis - Jing Yu; Yijing Yang; Tianwei Liu; Kun Huang; An Xu; Li Gong; Jing Liu; Fenghui Li; Denghui Zhu; Liqin Liu; Zhenming Lü (Journal of Oceanology and Limnology, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

Surface-water estradiol–benzo[a]pyrene mixtures: Transcriptomics in a PC12 neuronal differentiation model nominate an E2F1–PTPRO axis as a candidate mechanistic biomarker - Caiyun Sun; Peng Wang; Yu Xia; Mengyuan An; Shuang Liu; Chuanbing Wu; Wansheng Zhang; Wenwen Li; Yuhan Zhou; Junkai Hao; Liang Xu (Toxicology Letters, 2026)

Exosomal lncRNA ENSSSCG00000049656 regulates porcine oocyte maturation via the ssc-miR-500-3p/EGLN2 axis - Junzheng Zhang; Yuyang Zhang; Hao Li; Jie Wang; Zhiwei Yao; Kun Zhao; Yang An; Shunfa Yao; Qinglong Xu; Shuang Ji; Yi Jin (Theriogenology, 2026)

GDSL lipase complex ZmMS30/IPE2 coordinates fatty acid and phenylpropanoid metabolism to ensure exine foot layer formation in maize - Quancan Hou; Jinghua Niu; Shuangshuang Liu; Juan Zhang; Zhiwei Shui; Zhixian Xu; Ziwen Li; Lina Zhao; Xiaofeng Xue; Xueli An; Huabang Chen; Xiangyuan Wan (Science Bulletin, 2026)

Boosting multi-heavy metal sequestration in king grass: Unveiling the role of Serendipita indica symbiosis and the key root exudate GABA - Yali Duan; Jialiang Luo; Miaomiao Wang; Dong Li; Huiping Feng; Li Lin; Qianli An; Shunqing Xu; Zhiqiang Zhu (Journal of Environmental Sciences, 2026)

Quantifying multi-objective trade-offs in maize production and greenhouse gas emissions under brackish water irrigation using GAM–NSGA-II - Chenchen Wei; Yu Wang; Yanbing Chi; Peiling Yang; Cheng Yan; Yalong Li; Miaomiao Shi; Baokun Xu; Yang Xu; Miaoying An (Field Crops Research, 2026)

Heterogeneous activation of persulfate by PDA coated Fe@MXene for efficient degradation of dyeing wastewater - Wanxin Li; Dawu Shu; Fangfang An; Xin Qiao; Yueyong Dong; Chengshu Xu (Environmental Research, 2026)

High-sensitivity and ultra-wide-range flexible piezoresistive sensor with surface microsphere and gradient cell structure for human gait correction - Xiangfang Peng; Shengguo Gu; Wen Xiao; Yuhuan Lin; Shulei Wu; Shuai Wang; Bin Tan; Haoyang Mi; Suiyi Li; Zhixiang Cui; Yongchao Xu; Feifan Yi; et al. (Chemical Engineering Journal, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

Targeting angiopoietin-like protein 3 and interleukin-1β alleviated liver and kidney injury through attenuation of lipotoxicity and regulation of glycolipid metabolism in db/db mice - Shuwen Xu; Longfei Wang; Zihan Dou; Xiaozhi Hu; Zhonglian Cao; Yuanzhen Zhang; Xianhan Jiang; Tao Wu; Zhuojin Li; Yanyang Nan; An Zhu; Yu Bai; et al. (Inflammation Research, 2026)

Activating FcγRI inhibits RIG-I-mediated host antiviral innate immunity by FGR during PRRSV-ADE infection - Peng-li Xu; Yi-han Li; Fa-hao Li; Shi-jie Zhao; Wen Li; Jing Chen; Ping-an Xia; Yi-na Zhang (Veterinary Microbiology, 2026)

Mechanism of mineralization and medium-small earthquake occurrences constrained by high resolution shallow structures in Sanshui Basin, South China - Jinrui Liu; Weicheng Yang; Dongli Zhang; Weiyu Feng; Jian Xu; Ruizhi Jin; Qi 'an Pan; Siran Huang; Hao Li; Xuzhang Shen (Physics of the Earth and Planetary Interiors, 2026)

Comparative assessment of reproductive and intergenerational toxicity of perfluorooctanoic acid and hexafluoropropylene oxide trimer acid in zebrafish (Danio rerio) - Shenggan Wu; Xuehua An; Ting Xu; Dou Wang; Zhenlan Xu; Yuanxiang Jin; Xinquan Wang; Yun Li; Yanhua Wang (Journal of Hazardous Materials, 2026)

Nutrient accumulation and redox conditions shape lake bacterial communities: A dual-medium assessment of closed coal-mining subsidence versus natural lakes - Shuo Li; Lei Zhang; Wen Ge; Yijie An; Ting Song; Feng Xu; Hua Cai (Journal of Environmental Chemical Engineering, 2026)

A Non-Invasive stacked ensemble framework with shadow correction for Cost-Effective daylight illuminance prediction in buildings - Shanshan Li; Xinyue Xu; Haoran Wang; Yuheng Cao; Hongda An; Ziyang Wang; Sina A; Changhao Wang (Energy and Buildings, 2026)

Multi-scale quantile neural network for air quality index prediction - Shangrui Zhao; Weiqi Yu; Xi’an Li; Jing Xu; Jinran Wu (Theoretical and Applied Climatology, 2026)
Accurate forecasting of the Air Quality Index (AQI) is essential for mitigating the adverse environmental and public health impacts associated with air pollution. However, existing predictive models often exhibit limited robustness to extreme outliers and struggle to effectively capture multi-scale temporal dependencies and associated uncertainties. To address these challenges, this study proposes a novel Multi-scale Quantile Neural Network (MQNN) framework that integrates Fourier expansion for temporal feature extraction and the pinball loss function for probabilistic quantile estimation. Specifically, the AQI time series is first decomposed via Fourier expansion to capture multi-scale temporal dynamics. These transformed features are then processed through multiple parallel subnetworks, each trained to predict a distinct quantile using the pinball loss. The overall training objective aggregates the loss across all time steps and quantiles, with optimization proceeding until convergence. The proposed MQNN model is empirically evaluated using AQI datasets from five major cities in China. Experimental results demonstrate that MQNN consistently outperforms conventional machine learning and deep learning baselines, achieving higher accuracy and more reliable uncertainty estimation. Furthermore, the MQNN framework facilitates the identification of dominant pollutants, offering actionable insights for targeted air quality management and policy interventions. While the MQNN model has strong predictive capabilities, its computational cost remains high for high-dimensional inputs. Moreover, integrating external information may further improve prediction accuracy and enhance the model’s applicability in real-world scenarios.

The Regulating Effect of Weizmannia coagulans BC-G44 on Antibiotic-Associated Diarrhea and its Improvement on Gut Microbiota - Zhouyi Wang; Yinghan Xiang; Yafang Xu; Jiaxin An; Qianrui Wei; Yang Chen; Di Han; Zhanxi Hao; Huajun Li (Probiotics and Antimicrobial Proteins, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Unified quasi-solid electrolyte design for coupled stabilization of Zn anode and I2 cathode in aqueous Zn-I2 batteries - Meng’an Wang; Tao Li; Shicong Zhang; Hexian Ma; Yang Xu; Yi Shen; Chenyu Wei; Tao Zhang; Tianquan Lin (Science Bulletin, 2026)

Hydrogen sulfide-activatable intermolecular superoxide anion transfer for molecular afterglow luminescence imaging of bacterial resistance - Weina Xu; Weihao An; Zhongkun Wang; Meng Zhao; Qing Li; Qingqing Miao (Science Bulletin, 2026)

Tamarisk miRNA target genes TcSPL5 and TcNAC1 mediate the post-transcriptional responses of salt stress - Yang Zheng; Junwen Wang; Meng Xu; Mu Cao; Shaoyan Jiang; Jianwen Wang; Li-an Xu (Plant Science, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Mechanistic insights into structural evolution of goji berry (Lycium barbarum L.) during pulsed vacuum drying procedure via moisture migration and cell wall polysaccharide transformations - An-An Zhang; Li-Zhen Deng; Long Xie; Ze-Kang Peng; Ming-Qiang Xu; Wan-Liang Hao; Yu-Hao Jiang; Wen-Bin Ze; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Novel approach to binary protein construction via pulsed electric field-induced unfolding: Comprehensive enhancement of chickpea protein properties - Yongxin Teng; Xindong Xu; Boru Chen; Rui Wang; Ting Zhang; Xiangwei Zhu; Yonghui Li; Zhong Han; Xin-An Zeng (Food Hydrocolloids, 2026)

Probability-based dynamic amplification factor assessment of a hybrid cable-stayed suspension bridge under combined highway and railway loads - Jian-An Li; Zhitao Sun; Zichao Li; Dongming Feng; Jinjing Xu (Engineering Structures, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

Responses of soil bacterial community structure across mining age and soil depth scales in coal mining subsidence zones - Zhe Wang; Lei Zhang; Yijie An; Feng Xu; Shuo Li; Hua Cai (Plant and Soil, 2026)

Photovoltaic and Aquaculture Environments Consistently Reduce Bacterial Diversity but Divergently Influence Ecological Stability: New Insights from Subsidence Lakes - Xingchen Li; Lei Zhang; Yijie An; Sixu Gu; Feng Xu; Hua Cai (Environmental Management, 2026)

Quantitative alignment and study of low-frequency excitation parameters based on walnut tree (Juglans regia L.) shape characteristics - Jiale Cao; Heng Chen; Jianshuo An; Jingwei Wang; Latai Ga; Daochun Xu; Xiaopeng Bai; Wenbin Li (Biosystems Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Mitophagy dynamics during oxidative to reductive stress shift potentiates arsenite-induced malignant transformation potential in human keratinocytes - Qianlei Yang; Xingrun Li; Qi Kong; Yuqi Yang; Haixuan Xia; Rui Yan; Xiaoyun Zhang; Hui Lu; Ting Zhang; Chen Zhao; Bohan Xu; Koichi Kato; et al. (Journal of Hazardous Materials, 2026)

Novel green ternary deep eutectic solvents for efficient extraction of nitrogen compounds from oil - Yingying Zuo; Rui Zhou; Xiaohang Yang; Jian Wang; Xu Liu; Yushan Li; Zhengqi Liang; Boxing An; Fengjuan Niu (Journal of Environmental Chemical Engineering, 2026)

Enhanced biocoal production from tobacco stem through leaching coupled with hydrothermal carbonization - Jiayou Sun; Chi Xu; Qiang An; Shihao Meng; Xiang Meng; Jialin Yang; Hao Zhan; Zhengyong Xu; Shihui Zhang; Lijian Leng; Hailong Li (Journal of Environmental Chemical Engineering, 2026)

Multi-scale assessment of energy transition and emission patterns in industrial coastal regions - Ying Teng; Mingkun Bai; Xiran Lin; Jiajie Li; Tao Zhang; Shuyang Liu; Senyou An; Liangbin Xu; Pengfei Wang; Songbai Han; Jinlong Zhu; Jianbo Zhu; et al. (Fuel, 2026)

Cold plasma technology in food Systems: Mechanisms, multifunctional applications, and pathways to industrial adoption - Lang-Hong Wang; Haiqian Xu; Bing Yan; Boru Chen; Xin-An Zeng; Yanyan Huang; Jian Li (Food Control, 2026)

An efficient multi-objective optimization method for inter-basin water diversion based on the rotation vector method for exploring the convex objective space - Zekun Li; Bin Xu; Ping-an Zhong; Jiaying Tan; Ran Mo; Xinrong Wang; Zichen Ren; Guoqing Wang; Jianyun Zhang; Jiangyuan Li; Scott E. Boyce (Environmental Modelling & Software, 2026)

Bioactive nanoreactor-enhanced injectable polysaccharide hydrogels for tissue regeneration and scar suppression via multifactorial regulation in infected burn wounds - Junyao Li; Xiaochen Wu; Xintao Gao; Jingtong An; Qishan Xu; Xiangyan Chen; Yantao Li (Chemical Engineering Journal, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Substrate-independent surface/interface engineering for efficient water treatment membranes - Runliang Gao; Haoyang Wang; Yangxue Li; Xu Wang; Alicia Kyoungjin An; Lu Shao; Xiaobin Yang (Chemical Engineering Journal, 2026)

Heterologous expression of Pinus massoniana VNS2 enhances secondary cell wall deposition in poplar - Yating Tian; Kang Wang; Hao Rong; Meng Xu; Zhouxian Ni; Li-an Xu (Plant Cell Reports, 2026)

Role of Microglial Dysfunction in Parkinson’s Disease: From Multifactorial Causes to Neurodegeneration - Yuxiang Xu; Tingting Han; Yue Wu; Haixuan Liu; Keyuan Hou; Zhaowu An; Yongjie Li; Chaoyang Zhu; Song Wang; Jianshe Wei (Neuroscience Bulletin, 2026)

Design of asymmetric combined flow-guiding valve core structure in hydraulic spool valve - Zhao-tong Wang; Wen-qing Li; Xu-han Wang; Tong An; Zhen-hao Lin; Zhi-jiang Jin; Jin-yuan Qian (Annals of Nuclear Energy, 2026)

Pan-Cancer Analysis of ANO6 and Experimental Validation in Metastatic Melanoma - Yao An; Haoran Dong; Meishan Yan; Caixu Liu; Danfeng Hu; Qi Liu; Jingqiu Zhang; Xu Han; Zimeng Li; Minghui Xu; Li Chen; Quanzhi Zhang; et al. (Biochemical Genetics, 2026)

Target Abundance in Pharmacological Target-Mediated Drug Disposition (TMDD) for Small Molecules — A Proteomics Approach - Min Xu; Xuanzhen Yuan; Peizhi Li; Thanh Bach; Hao-Jie Zhu; Guohua An (The AAPS Journal, 2026)
The phenomenon of nonlinear pharmacokinetics (PK) mediated by a drug’s pharmacological target, also known as target-mediated drug disposition (TMDD), has been increasingly observed in small molecules in the past decade. TMDD class effect with remarkably similar nonlinear PK behaviors has been reported in 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) inhibitors, monoamine oxidase type B (MAO-B) inhibitors, and soluble epoxide hydrolase (sEH) inhibitors. We anticipated that the occurrence of TMDD class effect might be due to their target capacities falling within a specific range, where nonlinear PK mediated by target binding are more likely to be evident. To test our hypothesis, we employed a mass spectrometry (MS)-based global proteomics approach to quantify the absolute protein concentrations of 11β-HSD1, sEH, and MAO-B in different tissues across species. The estimated total amounts of 11β-HSD1, MAO-B, and sEH in humans were approximately 4994, 4629, and 4137 nmol, respectively. The comparable abundance levels of these proteins suggest that TMDD is more likely to be observed when a drug binds to a target within a specific range, potentially between 1000 nmol and 10000 nmol, which corresponds to nonlinear PK at doses of 1–10 mg for a compound with a molecular weight of 400 g/mol. Our study highlights the importance of early target quantification and provides valuable insights into predicting unusual nonlinear PK caused by TMDD. Additionally, this proteomics-based approach for quantifying absolute target capacity could serve as a valuable tool for both industry and academic researchers in investigating other pharmacological targets. Graphical Abstract

Geographic origin and post-invasion genetic divergence of Mytilus galloprovincialis in China - Jian'an Li; Ben Yang; Ahmed Mokrani; Mengmeng Xu; Xiaojie Han; Tim P. Bean; Robert P. Ellis; Shikai Liu (Marine Pollution Bulletin, 2026)

Mechanistic insights and application of SS/MS/C/CaO₂ composite for the simultaneous removal of ammonia nitrogen and multiple antibiotics - Jie Zhao; Chang Lu; Junzhao Liu; Yuze Han; Xiuwen Li; Jun Li; Wentao Li; Hongbin Xu; Jingqing Gao; Aimin Li; Shuqing An (Water Research, 2026)

Scale-up synthesis and antiviral mechanisms of novel fluorine-containing cytidine peptide compound SN15: Insights from transcriptomic and proteomic analyses - Miao Yu; Chuantao Xu; Yan Wang; Shidong Zhou; Jingwen Li; Zihao Xia; Mengnan An; He Liu; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Influence of local slip boundary condition on the hydrodynamic performance of hydrofoils for cross-domain vehicles at low Reynolds number - Di Peng; Baorui Xu; Changrong Yang; Jialin Liu; Chenxi You; Jiale Yan; An-Kang Gao; Pengyu Lv; Hongyuan Li (Ocean Engineering, 2026)

Carbonic anhydrase modulates photosynthetic responses to UV radiation in diatoms across temperature gradients - Xiangyu Li; Yuheng An; Juntian Xu; Yaping Wu; John Beardall (Journal of Photochemistry and Photobiology B: Biology, 2026)

Advanced physical-based techniques for the extraction and modification of plant protein: mechanisms, functions, and applications - Yi-han Cai; Meng-na Li; Hao-yue Xu; Fang Huang; Yu-xin Zhao; Jie-han Zhang; Yan-yan Huang; Xin-An Zeng (Food Chemistry, 2026)

Decoding the killer mushroom Amanita fuligineoides toxicity: from toxin profiling to organ injury mapping - Gangzheng Wang; Bei Hu; Liuying An; Xi Lei; Guoring Zhong; Lixia Gan; Chenghua Zhang; Taihui Li; Jianping Xu; Huaming Qin; Wangqiu Deng (Food Bioscience, 2026)

Improving the prediction performance of soluble solid content in bagged “Cuiguan” pear using Vis/NIR spectroscopy with spectral correction - Yiran Zhao; Qingqing Li; Changqing An; Kun Tao; Yida Yu; Huirong Xu (Food Control, 2026)

Wheat SLC25A4-7B negatively regulates drought tolerance by coordinating stomatal aperture size and abscisic acid content - Jie Tian; Pengpeng Zhao; Dingli Hong; Zhongni Wang; Muhammad Arif; Chang An; Ling Xu; Mingjian Ren; Luhua Li; Ruhong Xu (Planta, 2026)

Measuring intercontinental-scale geopotential difference using atomic clock frequency comparison with PPP technique - Kuangchao Wu; Wen-Bin Shen; Hok Sum Fok; Zengzeng Lian; Pengfei Zhang; Lihong Li; Lei Wang; An Ning; Rui Xu; Ziyu Shen (Advances in Space Research, 2026)

Study on Aeromagnetic Anomaly Characteristics and Tectonic Ore-Controlling Effects in Leiwuqi-Zuogong Area, Tibet - Jian-chun Xu; Yan-xu Liu; Wen-yong Li; An-qi Cao; Shan Gao; Xue Yang (Applied Geophysics, 2025)

Integrated probabilistic forecasting framework for long-term reservoir outflow through dynamic coupling of meteorological–hydrological–engineering processes - Jiaying Tan; Bin Xu; Jian Zhu; Ping-an Zhong; Ran Mo; Jiangyuan Li; Yuanheng Dong; Xinman Qin; Jiayi Jiang; Huili Wang; Lingwei Zhu (Journal of Hydrology, 2025)

Significant chlorophenol formation during cobalt(II)/peracetic acid oxidation processes: The role of in-situ formed free chlorine - Zishi An; Baoqiang Hao; Renyuan Zhang; Wenjun Xu; Xiaoqing Li; Genye He; Wenfeng Zhou; Haixiang Gao; Jing Li (Journal of Environmental Chemical Engineering, 2025)

Ambient-dried polymer aerogel engineered via interparticle “stringing” towards ultrahigh robustness, flame retardancy and harsh-environment durability - Ting-Ting Li; Ting Wang; Chengxu Xu; Xue Gou; Xi-Ping Huang; Si-Yao Zhong; Zhi-Cheng Fu; Jinni Deng; Wenli An; Hai-Bo Zhao; Ming-Jun Chen (Chemical Engineering Journal, 2025)

Elucidation of the biodegradation pathways of polyurethane and polyethylene terephthalate by a Fusarium strain enriched from soil-plant systems - Eyalira Jacob Okal; Yanfei Wu; Shahid Iqbal; Zhaorui Liu; Yuwei Hu; Na Hu; Tingfang Zhong; Jingxian Li; Dongmei Yu; Bishal Gurung; Dong Liu; Peter Mortimer; et al. (Bioresource Technology, 2025)

Ammonia inhibition in anaerobic digestion and weakly electrical stimulation strategies: Exploring mitigation mechanisms and economic benefits-A review - Jiao Li; Yuchen Zhang; Ruixiang Zou; Wenhui Sun; Wenhui An; Eric Lichtfouse; Suyun Xu; Hongbo Liu (Bioresource Technology, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Botryosphaeria dothidea causes leaf spot disease on Rosa roxburghii in China - Qinyi Hu; Taotao An; Wei Jia; Junxian Chen; Ying Xu; Zhu Li; Haixia Ding (Crop Protection, 2025)

3D reconstruction of orchard scenes based on UAV images and neural radiance fields - Heng Chen; Jiale Cao; Jianshuo An; Wenbin Li; Xiaopeng Bai; Daochun Xu (Biosystems Engineering, 2025)

Stability of RL-modified n-FeS and its mechanisms for Cr(VI) removal efficiency - Kaipian Shi; Junfeng An; Lin Xu; Li Yin; Chunqing Peng; Yong Zhang; Shiyin Li; Lixiao Ni (Journal of Water Process Engineering, 2025)

Hydrogeochemistry and geothermometry of carbonate aquifers at the southern margin of the northern China coalfield: Insights from major ions and environmental isotopes - Haitao Zhang; Guangquan Xu; Hongbin Zhan; Xiaoqing Chen; Xu Li; Zhuting Wang; Kai Wang; Jianghui He; Zixuan Li; An'an Zhao; Hao Wang (Groundwater for Sustainable Development, 2025)

Identification and functional characterization of Cyprinus carpio cGAS reveals its pivotal role against viral infection - Chun Li; Guoli Hou; Liang Hu; Yang Xu; Qiushi Zhang; Xinyu Liang; Yong-An Zhang; Junhua Li (Fish & Shellfish Immunology, 2025)

Bioactive glass with integration of hyperthermia to manipulate pH-responsive release of chemotherapeutic agent for osteosarcoma combating and time-sequential reconstruction of bone homeostasis - Qingshan Li; Yuyang Gao; Runmeng Li; Hao Li; Changjiang Yang; Honglong Li; Limin Zhao; Bochen An; Gang Han; Jiying Chen; Haobo Pan; Quanyi Guo; et al. (Chemical Engineering Journal, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Investigation of the South Atlantic Anomaly (SAA) by proton flux variabilities based on 6 years’ CSES data - Lu Wang; Zhenxia Zhang; Xinqiao Li; Zhenghua An; Yanbing Xu; Ping Wang; Hong Lu; Xiaoyun Zhao; Dali Zhang; Xiaohua Liang; Zhiqiang Ding; Shujie Li; et al. (Science China Earth Sciences, 2025)

Integrated proteomic, chemical forms, and distribution analysis reveals NaCl-mediated detoxification of cadmium in Suaeda salsa - Honglei Jia; Shutong Wang; Jie Xu; Fengyun Yao; Wen Yuan; Haodong An; Jisheng Li; Chengtao Li (Plant Cell Reports, 2025)

Unravelling the genetic landscape of Channa argus in Shandong Province: Insights into population differentiation, adaptation and conservation from whole‐genome resequencing - Li An; Qinglei Meng; Xuesa Dong; Shuren Zhu; Chao Wang; Xiao Xu; Xiuyun Feng; Yuqing Liu; Jiaren Yan; Longgang Zhang (Journal of Fish Biology, 2025)
The snakehead ( Channa argus ) is an economically important freshwater fish species. Understanding how geographical isolation affects population differentiation is important for understanding the processes that shape biodiversity. We examined four wild populations [Dongping Lake (DP), Nansi Lake (NS), Yihe River (YH) and Yellow River Estuary (HH)] and an aquaculture population [Weishan Lake (WL)] in Shandong Province using whole‐genome resequencing for the first time. This approach provided deeper insights of genetic variation compared to previous studies with lower genome coverage. We identified single nucleotide polymorphisms (SNPs) and insertion–deletion (InDel) variants among the five populations. A total of 106,172 DNA variants were located in the exonic gene region, with 53,415 causing nonsynonymous mutations, 9757 resulting in frameshift mutations and 2345 leading to a loss or gain of stop codons. Polymorphic information content (PIC) analysis showed moderate polymorphism across all populations, with an increase over the past decade, likely due to reduced human interference. Genetic diversity indexes ( H O , H E , H′ and π ) showed minimal variation among populations, suggesting similar environmental pressures and low levels of inbreeding. F is values indicated that the WL and NS populations met the neutral expectation of heterozygosity, whereas other populations exhibited higher heterozygosity potentially due to geographical factors. Phylogenetic tree analysis, principal component analysis (PCA) and population structure analysis confirmed genetic clustering aligned with geographical distribution. The F st values indicated moderate genetic differentiation, with gene flow observed between the DP and WL populations likely due to artificial introductions. The WL population exhibited strong signs of artificial selection. Functional enrichment analysis revealed adaptive differentiation in osmoregulation‐related genes in the HH population, whereas the WL population showed selective pressure in genes related to oxygen transport in the blood, suggesting the influence of aquaculture and environment on genetic adaptation. This study highlights the role of geographical isolation in population differentiation and emphasizes the importance of habitat connectivity in maintaining gene flow and genetic diversity. The findings indicate no significant human‐induced isolation in the major water bodies of Shandong Province, which benefits the conservation of C. argus and provides valuable insights for the sustainable management of wild populations.

Unmanned Aerial Vehicle (UAV) Aeromagnetic System Based on Fluxgate Sensor and Its Applications - Nan Zhang; Li-zhong Xu; Tian-hao An; Jin-ge Zhang; Hua Guo (Applied Geophysics, 2025)

Corrigendum to “Study on cable flame spread in utility tunnel under different reverse ventilation and cable layer spacing” [Tunn. Undergr. Space Technol. 162 (2025) 106671] - Tongcheng Zhang; Xiaoshan Wang; Zhe Wang; Junyi Li; Weibin An; Feixiang Xu; Weiguang An (Tunnelling and Underground Space Technology, 2025)

Ceritinib (LDK378) inhibits laryngeal squamous cell carcinoma progression via regulating ROS-induced mitochondrial apoptosis and inducing oxidative stress - Yue Wang; Xiaoli Ren; Pengyan Liu; Ran An; Wenjing Li; Licheng Xu; Yaoyao Dong; Xiaolin Xu; Yi wang; Lei Zhang; Linli Tian (Toxicology and Applied Pharmacology, 2025)

Exploring the impact of follicular fluid exosomes on porcine cumulus cell and oocyte function: Regulatory network analysis based on the ENSSSCG00000042788/ssc-miR-504/PDHA1 axis - Junzheng Zhang; Shuang Ji; Yue Han; Yuyang Zhang; Hao Li; Shunfa Yao; Qinglong Xu; Kun Zhao; Jie Wang; Zhiwei Yao; Yang An; Yi Jin (Theriogenology, 2025)

A new genus and species of Susumaniidae (Insecta: Phasmatodea) from the Middle Jurassic of Shaanxi Province, Northwest China - Qi-Ming Guo; Chun-Peng Xu; André Nel; An-Cheng Peng; Zhi-Gang Wen; Ting Li; Rui Fang; Da-Ran Zheng (Palaeoworld, 2025)

Modeling the cumulative impact of minor impoundments on watershed hydrology: Enhancements to the Xin’anjiang model - Yiwen Wang; Weifeng Liu; Feilin Zhu; Bin Xu; Weiyu Li; Jianjie Tong; Ping-an Zhong (Journal of Hydrology, 2025)

Zoonotic pathogen-driven antibiotic resistance emerges in urban soils: A large-scale study in 13 cities across China - An Xie; Wenjuan Xu; Zhi-Peng Li; Bin Wang; Alexei V. Tiunov; Patrick O'Connor; Jian-qiang Su; Qiansheng Huang; Faith Ka Shun Chan; Matthias C. Rillig; Xin Sun (Journal of Hazardous Materials, 2025)

Self-potential gradient inversion based on a hybrid weighting strategy - Hao Li; Yi-an Cui; Pu Wang; Pengfei Zhang; Jing Xie; Xiangbo Yang; Wenxuan Duan; Yuxin Xu; Jianxin Liu (Journal of Applied Geophysics, 2025)

Ecotoxicological effects of phthalate esters: A review - Ying Xu; Mengyuan Pei; Zhuofan Li; Jiake Xu; Xiaoqing Yang; Le’an Chen; Cheng Zhang; Lusheng Zhu; Jun Wang; Peng Gao (Environmental Pollution, 2025)

Applications and prospects of tin-based electrode materials in lithium/sodium ion capacitors - Juan An; Mingyuan Pang; Qianqian Yang; Haohao Zhang; Jiajia Ye; Zhen Kong; Min Yang; Dan Xu; Yen Leng Pak; Wei Liu; Jibin Song; Guoxing Li (Desalination, 2025)

Two-photon phototherapy-mediated activation of natural killer cell immunity for targeted elimination of post-treatment residual hepatocellular carcinoma - Yubo Tan; Yibo An; Yisheng Peng; Man Li; Ziying Wang; Renyuan Liu; Dazhuang Xu; Xinyu Tan; Peiyu Wang; Yaohui He; Bo Li; Gang Liu; et al. (Chemical Engineering Journal, 2025)

Flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2025)

Subchronic exposure to CeCl3 promotes macrophage ferroptosis and atherosclerotic plaque formation by inhibiting the Keap1/Nrf2/GPX4 pathway - Baoping Xie; Liuyan Xin; Wen Liu; An Li; Qi Jin; Shuping Xu; Gonghua Hu (Chemico-Biological Interactions, 2025)

Pan-cancer analysis of acetylcholinesterase (AChE) expression by a data-driven approach: future directions of AChE in cancer neuroscience - Jiahui An; Heidi Qunhui Xie; Zhen Yan; Xin Chen; Ruihong Zhu; Guanglei Yang; Li Xu; Zrinka Kovarik; Karl Wah Keung Tsim (Chemico-Biological Interactions, 2025)

Mesenchymal Stem Cells Derived from Different Adipose Tissue Depots Ameliorate Severe Acute Pancreatitis by Inhibiting NF-κB/NLRP3/Caspase-1 Pathways - Ao Wang; Yu An; Xuefei Wang; Wenfeng Gou; Feifei Xu; Yanli Li; Cong Wang; Zhengwei Tu; Wenbin Hou; Yunfeng Cui (Stem Cell Reviews and Reports, 2025)

Integrating Attention Mechanisms in Graph Neural Networks for Marine Oil Spill Detection - Fengjing Cai; Yue Wang; Zhuangcai Tian; Xi’an Li; Jing Xu; Yuming Mo; Shaotong Zhang; Jinran Wu (Journal of Ocean University of China, 2025)

Standing at the crossroads: How does amino acids function in the crosstalk between pancreas and the kidney under exposure to per- and polyfluoroalkyl substances? - Ming Yang; Ziwen An; Xiaoqing Xing; Yayuan Mei; Haoran Li; Jiaxin Zhao; Zhenzhen Tan; Yanbing Li; Jingjing Zhao; Jiayin Zhao; Meiduo Zhao; Jing Xu; et al. (Journal of Hazardous Materials, 2025)

Effect of PFAS serum exposure pattern on the lipid metabolism: Time to step-forward in causal inference in epidemiology - Ming Yang; Ang Li; Yayuan Mei; Haoran Li; Ziwen An; Quan Zhou; Jiaxin Zhao; Yanbing Li; Kai Li; Meiduo Zhao; Jing Xu; Huicai Guo; et al. (Journal of Environmental Sciences, 2025)

Comparative analysis of sheep, goat, and cow milk based on non-targeted metabolomics - Jiaxin Liu; Zhongshi Zhu; Yanping Huang; Jianping Qin; Li Wang; Mengyao Wei; Xiaorui Liu; Liang Xu; Hao Yuan; Xiaopeng An; Lei Zhang; Yuxuan Song (International Dairy Journal, 2025)

Straw residue incorporation promotes soil organic carbon accumulation and enhances the effect of subsoiling on plant growth - Weijun Zhang; Xu Liu; Lars J. Munkholm; Tingting An; Hongdan Li; Xiaoqian Xu; Shuangyi Li; Chang Peng; Jingkuan Wang (Geoderma Regional, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Constructing the linear adsorption of *CO and suppressing hydrogen evolution by alkaline earth metal for efficient CO2RR - Xupeng Qin; Qizheng An; Shen Cheng; Honglei Chen; Wanlin Zhou; Haixin Sun; Yuhao Zhang; Yanzhi Xu; Changli Li; Yaling Jiang; Jingfu He; Qinghua Liu (Chemical Engineering Journal, 2025)

A novel system combining bilateral comb anode-based anodic oxidation and FeOCl@AC plate-based cathodic electro-Fenton for improved mass transfer and efficient treatment of coking wastewater - Jiajun Li; Haiming Yang; Jinyu Zhang; Huanhuan Xu; Yufan Liu; Shouyuan Peng; Jiayi Wang; Jiaotong Liu; Xin Geng; Hongyang Zhao; Guozhong Xu; Baigang An (Chemical Engineering Journal, 2025)

Potential prognostic biomarker of OSBPL10 in pan-cancer associated with immune infiltration - Jiapeng Qi; Kun Yu; Bei Liu; Yan Wang; Wei Wang; Ran An; Chaojun Wang; Na Li; Dongqian Xu; Lin Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Oil and gas basin analysis based on airborne gravity and magnetic data - Yan-Xu Liu; Wen-Yong Li; Guo-Qing Ma; An-Qi Cao; Shan Gao; Ning Wang; Wen-Fen Lu; Li-Jie Wang; Cheng Yang (Applied Geophysics, 2025)

Oxygen vacancies-mediated the peracetic acid activation to selectively generate 1O2 for water decontamination - Yi Chen; Qian Li; Ruidian Su; Yixuan Gao; Ning An; Yu Rong; Xing Xu; Defang Ma; Yan Wang; Baoyu Gao (Water Research, 2025)

Study on cable flame spread in utility tunnel under different reverse ventilation and cable layer spacing - Tongcheng Zhang; Xiaoshan Wang; Zhe Wang; Junyi Li; Weibin An; Feixiang Xu; Weiguang An (Tunnelling and Underground Space Technology, 2025)

Cadmium exposure causes trophoblast abnormal syncytization and endocrine dysfunction in preeclampsia - Weilong Lin; Xuemeng Li; Xiangyou An; Jiancai Yin; Ziyan Zhao; Xiaorui Yan; Rong Xu; Baojing Zhao; Xue Du; Huiru Cheng; Zhen Yu; Yuanyuan Yang (Reproductive Toxicology, 2025)

Bioactive terpenoids and sterols from the fruiting bodies of Fomitopsis pinicola - Huan Yu; Qian Chen; Tian-Chi Xu; Yue Wang; Wen-Feng Xu; Min Li; Xu Zhang; Chuan Zhao; Dong-Li Zhang; Peng-Fei Jin; Shao-Yong Li; Sheng-An Tang (Phytochemistry, 2025)

Identification of Pb-responsive GST transcripts in Salix integra and Pb tolerance of transgenic plants overexpressing SiGSTU55 - Yue Xin; Ruifang Huang; Meng Xu; Li-an Xu (Journal of Hazardous Materials, 2025)

Genomic localization and immune response of IgT in grass carp (Ctenopharyngodon idellus) - Wen-Tao Li; Bin Liu; Jie Wang; Yong-An Zhang; Xu-Jie Zhang (Fish & Shellfish Immunology, 2025)

Three-dimensional reconstruction and parameters extraction of walnut (Juglans regia L.) branches based on Neural Radiation Fields - Wei Zhu; Runchen Ma; Jianshuo An; Wenbin Li; Xiaopeng Bai; Daochun Xu (European Journal of Agronomy, 2025)

The molecular mechanism for improvement of coastal silt soil by the intercropping model of Suaeda glauca (Bunge) Bunge and Sesbania cannabina (Retz.) Pers - Xiaochi An; Ying Li; Yinhua Cao; Zaifeng Wang; Min Xu; Bin Lian (Plant and Soil, 2025)

Detrital Zircon U-Pb Age Analysis of Late Pliocene Deposits from the Lower Yangtze River, South China: Implications for Sedimentary Provenance and Evolution of the Yangtze River - Xu Lin; Yuxuan Pang; Chang’an Li; Jing Liu-Zeng; Marc Jolivet; Haijin Liu; Chengwei Hu; Xiaokang Chen (Journal of Earth Science, 2025)

Associations of accelerated epigenetic aging with cancer and mortality risk in the USA - Tongyan An; Hui Zhang; Yaqian Xu; Chongyu Ding; Yulu Gong; Darong Hao; Jing Wang; Xinyi Zhang; Tianlang Tong; Zhaojun Wang; Shuaiyin Chen; Xiangwei Li (GeroScience, 2025)

Isolation and identification of Diaporthe phoenicicola causing leaf spot on Rosa roxburghii in China - Junxian Chen; Liangyu Xiao; Taotao An; Wei Jia; Qinyi Hu; Ying Xu; Zhu Li; Haixia Ding (Crop Protection, 2025)

Geochemical characteristics of light hydrocarbons generated in thermochemical sulfate reduction: Results from three series of simulation experiments - Zhenyu Sun; Jian Chen; Wanglu Jia; Qiang Wang; Jie Xu; Xin Li; Jianghu Yang; Ping'an Peng (Marine and Petroleum Geology, 2025)

Morphological characteristics and evolution processes of the blowouts on fine-grain armored paleodunes in the eastern Qaidam Basin, Tibetan Plateau - Dehua Xu; Ping An; Jiyan Li; Lupeng Yu (Geomorphology, 2025)

Enhancement of chickpea protein functionalities through higher-intensity pulsed electric field: Insights into protein aggregations and structural changes - Yongxin Teng; Yabin Wang; Xindong Xu; Rui Wang; Boru Chen; Langhong Wang; Fuchao Zhan; Zhong Han; Yonghui Li; Xiangwei Zhu; Xin-An Zeng (Food Hydrocolloids, 2025)

3D-printed CL-20-based energetic composites with interpenetrating polymer networks for enhanced mechanical property and microscale detonation performance - Handong Shi; Shijiao Li; Kai Han; Chuanhao Xu; Lei Gao; Fan Liao; Yanpeng Lv; Yurong Zhang; Chongwei An (Chemical Engineering Journal, 2025)

Electronic state reconfiguration of NiMoCox boosts electrocatalytic upcycling of polyethylene terephthalate plastic wastes for simultaneous production of formate and green hydrogen - Shaofeng Wang; Shuaidong Li; Yutong Li; Yue Xu; Zhaomeng Wu; Yingjian He; Yongwei Zhao; Zheer An; Ying Lan; Yanxiao Hu; Jingzi Zhang; Yan Huang; et al. (Chemical Engineering Journal, 2025)

Type-A and -C response regulator genes positively impact rice plant height and panicle architecture - Chenyu Rong; Renren Zhang; Jing Xie; Jieru Li; Tiantian Yan; Ziyu Liu; Yuexin Liu; Ruihan Xu; Xi’an Shi; Xuebin Zhao; Jiali Song; Yayi Meng; et al. (Plant Cell Reports, 2025)

Chemical constituents from the stems of Erythropalum scandens - Qiao-dan Pan; Yuan-he Huang; Li-yang Zhao; Wei-rui Wang; Bing-an Wei; Ying-ying Xu; Xian Wei (Phytochemistry Letters, 2025)

Impacts of grazing intensity on soil properties and carbon content in Xilamuren Grassland - Xu Li; Chunchun An; Xiaoqian Li; Qicong Wu; Xinchuang Chen; Jianying Guo; Tianming Gao; Huaichang Wang; Zhi Dong (Journal of Environmental Management, 2025)

Bottom-up self-assembly of Ti3C2T /SA aerogel for highly efficient dyes wastewater purification - Boxing An; Feihong Chu; Yaze Zhang; Xu Liu; Yushan Li; Beiyun Liu; Haiyan Liu (Journal of Environmental Chemical Engineering, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

Unexpectedly high diversity of parabasalids in captive snakes from China - Zhouchun Li; Yilei Zhang; Lijie Tian; Xinglong Song; Xinyuan Wang; Genhong Wang; Haofeng An; Olalekan Opeyemi Ayanniyi; Qianming Xu; Congshan Yang (European Journal of Protistology, 2025)

The role of electroactive biofilms in enhanced para-chlorophenol transformation collaborated with biosynthetic palladium nanoparticles - Shaofeng Zhou; Yanjing Li; Shan Yang; Lizhou Lin; Tongchu Deng; Cuifen Gan; Wenwen An; Meiying Xu (Environmental Pollution, 2025)

Exploring the distribution and transmission mechanism of ARGs in crab aquaculture ponds and ditches using metagenomics - Chao Li; Yun-xiang Zhu; Xiao-xiao Shen; Yuan Gao; Ming Xu; Meng-kai Chen; Ming-yang An (Environmental Pollution, 2025)

Corrigendum to “Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration” [Chem. Eng. J. 497 (2024) 154433] - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2025)

Regulating effect of wooded channels on debris flows - Xi’an Wang; Jiangang Chen; Xiaoqing Chen; Huayong Chen; Wanyu Zhao; Xiangning Li; Wenjing Xu (Landslides, 2025)

Effects of carbon sources on nitrite removal and microbial diversity in mariculture water - Zhen Ding; Meiling An; Hongli Xu; Zhongping Xu; Ning Fu; Lushan Wang; Li Zhang; Guoping Li (Biologia, 2025)

Fate and transformation of psychotropic drugs in urban wastewater systems and receiving rivers via the integration of targeted and suspect screening analysis - An-Guo Wang; Jin-Na Zhang; Li-Xin Hu; You-Sheng Liu; Guang-Guo Ying; Yin-Xiu Liang; Mei-Ying Xu; Zhi-Qiang Yu (Water Research, 2025)

Spatiotemporal transcriptome atlas of developing mouse lung - Xiaogao Meng; Wenjia Li; Jian Xu; Yao Yao; An Gong; Yumeng Yang; Fangfang Qu; Chenkai Guo; Hui Zheng; Guizhong Cui; Shengbao Suo; Guangdun Peng (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Pronounced advance on typhoon track forecast with global convection-permitting model - Jun Gu; Chun Zhao; Gudongze Li; Jiawang Feng; Mingyue Xu; Qiuyan Du; Zihan Xia; Yubin Li; Guanghua Chen; Xiaoyu Hao; Junshi Chen; Hong An (Science Bulletin, 2025)

2,4,6-trinitrotoluene induces neurotoxicity by affecting the G protein pathways in Caenorhabditis elegans - Ying Li; Yanping Zhou; Chunyan Wang; Yaguang Nie; Yongbing Zhu; Sanping Zhao; Lijun Wu; An Xu (NeuroToxicology, 2025)

Transcriptomic profiling revealed the regulatory pathways and key genes associated with cold tolerance in two eel gobies - Jing Liu; Yantao Liu; Tianwei Liu; Cheng Zhao; Yuzhen Wang; Kun Huang; An Xu; Liqin Liu; Li Gong; Zhenming Lü (Journal of Thermal Biology, 2025)

A novel Gordonia sp. PS3 isolated from the gut of Galleria mellonella larvae: Mechanism of polystyrene biodegradation and environmental toxicological evaluation - Luhui Xu; Xuejiao An; Huoyong Jiang; Rui Pei; Zelin Li; Jiehao Wen; Wenjie Pi; Qinghua Zhang (Journal of Hazardous Materials, 2025)

New insight of surface water disinfection by Fe2+-SPC: Important role of carbonate radical and the influence of carbonate/bicarbonate ions on free radicals balance - Zixiao Ren; An Ding; Xu He; Piotr Oleskowicz-Popiel; Guibai Li; Heng Liang; Huu Hao Ngo; Wei Qiu (Journal of Environmental Management, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Rational design of phospholipase D to enhance thermostability and catalytic activity for efficient biocatalytic phosphatidylserine synthesis - Peng Zhang; Xin-An Mao; Xiao-Li Kong; Jin-Song Gong; Zi-Kai Wang; Chang Su; Heng Li; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Food Chemistry, 2025)

Vacancy engineering in transition metal selenides for long-lasting and fast-charging Na-ion batteries - Changsheng An; Jialing Liu; Chen Xu; Chi Zhang; Ruiting Li; Shumin Zhang; Shiying Zhang; Jinbo Li; Chao Cai; Xing Ou (Chemical Engineering Journal, 2025)

Multiple stimuli-responsive circularly polarized luminescent bio-composite films by coassembling cellulose nanocrystals and curcumin - Shaoyi Cao; Jingpeng Wang; Wenye Sun; Bang An; Mingcong Xu; Sha Luo; Chunhui Ma; Haipeng Yu; Zhijun Chen; Jian Li; Wei Li; Shouxin Liu (Carbohydrate Polymers, 2025)

New perspectives on water chemistry classification of travertine/tufa - Qunwei Dai; Ting Zhang; Dejun An; Jingwen He; Jie Cui; Qiongfang Li; Ronglin Xu; Faqin Dong; Zheng Dang; Qianxi Song (Applied Geochemistry, 2025)

Comparative mitogenomes of Amblyopinae (Gobiiformes: Gobionellidae) and freshwater adaptation in Taenioides sp. - Li Gong; Kaixin Wang; Tianwei Liu; An Xu; Nannan Zhang; Wenchao Wu; Liqin Liu; Jing Liu; Fenghui Li; Zhenming Lü (Acta Oceanologica Sinica, 2025)

Gastrodin Protects Neuronal Cells Against Oxidative Stress Through miRNA-125b-5p/Mamdc2 Axis - Lei Hu; Chao Lin; Renfu Li; Shouying Xu; Qiang Xu; Zihao An; Chao Tang (NeuroMolecular Medicine, 2025)

Solar evaporator coupled with strong/weak convection and its cascade utilization - Zhengtong Li; Jia-Han Zhang; Jing Zhang; Peng Yan; Tao Yang; Chao Yang; Peng Lin; Taotao Meng; Meng An; Yingtang Zhou; Xingtao Xu (Science Bulletin, 2025)

Long-term suppression of Microcystis aeruginosa by tannic acid: Risks of microcystin pollution and proteomic mechanisms - Li Yin; Kaipian Shi; Yu Yin; Yong Zhang; Lin Xu; Junfeng An; Chunqing Peng; Conghui Wang; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

The released micro/nano-plastics from plastic containers amplified the toxic response of disinfection by-products in human cells - Han Li; Tong Wang; Yemian Zhou; Jing He; Ruoyun Dong; An Xu; Yun Liu (Food Chemistry, 2025)

A review of antibiotic resistance genes in major river basins in China: Distribution, drivers, and risk - Wenjia Li; Bin Wang; Tao Wang; Jiang Li; Junmin Qi; Jiwei Luo; Ting Zhang; Xiaoyi Xu; Li'an Hou (Environmental Pollution, 2025)

Effect of turbulent diffusion parameters optimization on O3 simulation in Beijing-Tianjin-Hebei and surrounding areas - Lu Yanting; Zhao Xiujuan; Li Yuhuan; Xu Jing; Miao Shiguang; An Xingqin (Atmospheric Pollution Research, 2025)

Modified Carbon-Based Fe (II)- ZIF Nanomaterials as a Highly-Selective Adsorbent for Phosphate Removal - Xu Liu; Yushan Li; Hao Zhou; Boxing An; Xingyu Yang; Cong Liu; Haiyan Liu; Hai Liang; Zhengqi Liang; Liansheng Li; Guicheng Li; Yingying Zuo (Water, Air, & Soil Pollution, 2025)

IRF4 Knockdown Inhibits the Chronic Rhinosinusitis Without Nasal Polyps Development by Regulating NLRP3/Caspase-1/GSDMD-Mediated Pyroptosis - Jun Xu; Jiahui Li; Xiaoya Wang; Yunsong An; Wenlong Liu; Renzhong Luo; Changzhi Sun (Biochemical Genetics, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

A Multi-Resolution Sequence Method with Strong Constraints for Marine Gravity Matching Navigation - Ning Mao; An Li; Jiangning Xu; Fangjun Qin (Journal of Marine Science and Engineering, 2025)
The navigation and positioning of underwater vehicles is challenging work, especially when there is already a large initial position error, and there is an increasing concern about how to quickly correct the position error. To enhance positioning accuracy under large initial positioning errors, this paper proposes a multi-resolution sequence method with a strong constraint marine gravity-matching navigation algorithm and validates it through field experiments. First, the fundamental principles and common optimization approaches of the standard Terrain Contour Matching (TERCOM) and Iterative Closest Contour Point (ICCP) algorithms are introduced, the limitations of the sequence-matching algorithms are analyzed, and a multi-resolution sequence-matching fusion framework is designed. Then, the constrained models incorporating positional, navigational, and gravitational parameters are designed, and a strongly constrained multi-resolution sequence-matching algorithm is proposed. Finally, the performance of the method is verified by three field test trajectories with an initial position error of about 6 nautical miles. The field test results show that the proposed method has better accuracy and reliability under large initial position errors.

Experimental investigation and application on mechanical properties of tunnel linings under different blockage rates of drainage system in a karst tunnel - Wangping Qian; Bo Wang; Dingwei Luo; An Xu; Shuchen Li (Tunnelling and Underground Space Technology, 2025)

Orbital stabilisation effect in Sb-based single-atom catalyst - Kexin Song; Binbin Yang; Qing Liang; Wengang An; Jielu Yu; Zhiwen Chu; Fuxi Liu; Zhou Jiang; Boning Xu; Wenwen Li; Wei Zhang; Weitao Zheng (Science Bulletin, 2025)

Uncovering toxin production and molecular-level responses in Microcystis aeruginosa exposed to the flame retardant Tetrabromobisphenol A - Li Yin; Yu Yin; Lin Xu; Yong Zhang; Kaipian Shi; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

Dioxin-like effects of an emerging contaminant 1,3,6,8-tetrabromocarbazole on the myogenic differentiation of mouse C2C12 cells - Guanglei Yang; Tong Xu; Di Hao; Ruihong Zhu; Jiahui An; Yangsheng Chen; Li Xu; Bin Zhao; Heidi Qunhui Xie (Environmental Research, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Synergy of dual dopants and nitrogen defects in graphitic carbon nitride for boosting sustainable photocatalytic inactivation efficiency towards antibiotic-resistant bacteria - Weixuan Li; Wanjun Wang; Chao Wang; Yiming Huang; Wenhai Liu; Weina Zhao; Zhe Xu; Guiying Li; Taicheng An (Chemical Engineering Journal, 2025)

De-SUMO1ylated hexokinase 1 selectively degraded by ubiquitin-proteasome pathway promotes boar sperm capacitation in vitro - Shunfa Yao; Qinglong Xu; Yanqiu Lv; Yuyang Zhang; Hao Li; Junzheng Zhang; Zhiwei Yao; Yang An; Xuan Chen; Yi Jin (Animal Reproduction Science, 2025)

Production and evaluation of a bivalent adjuvant inactivated vaccine against infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus - Zhen Zhang; Chunyan Guan; Jingzhuang Zhao; Jingnan Lin; Yizhi Shao; Linfang Li; Tongyan Lu; Peng Chen; Yong-An Zhang; Liming Xu (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Phagostimulant MTSG supplementation benefits growth-promoting and defensive effects of Rhodobacter azotoformans on Chinese mitten crab Eriocheir sinensis - Xurui Zheng; Li He; Lefu Wen; La Xu; Youhong Wang; Haipeng Cao; Chunlei Gai; Jian An (Journal of Invertebrate Pathology, 2025)

Assessment of microbial contamination in various processing rooms using culture-dependent and 16S rRNA methods in a commercial kitchen in eastern China - Honggang Lai; Minjun Liu; Xia Chen; Fangzhe Ren; Mingshu Xu; Xin-an Jiao; Jinlin Huang; Qiuchun Li (Food Control, 2025)

Assessing the impact of 2022 extreme drought on the Yangtze River basin using downscaled GRACE/GRACE-FO data obtained by partitioned random forest algorithm - Lilu Cui; Yu Li; Bo Zhong; Jiachuan An; Jiacheng Meng; Haoyang Guo; Chuang Xu (International Journal of Remote Sensing, 2025)

Experimental Study on the Flow and Diffusion Laws of Heterogeneous Gangue Slurry in Mining Space - Nan Zhou; Jixiong Zhang; Jianfei Xu; Haodong Wang; Sixu Liu; Meng Li; Tailong An (Rock Mechanics and Rock Engineering, 2025)

Top-to-south shear at the base of the eastern Tethyan Himalayan Sequence during the Eocene-Oligocene Himalayan orogeny - Zhiqin Xu; An Yin; Hua Xiang; Qin Wang; Guangwei Li; Hanwen Dong; Hui Cao; Jianguo Gao (Tectonophysics, 2025)

Temporal-spatial characteristics and driver pattern of methane emission in heterogeneous Chinese cities - Chong Xu; Jianda Li; Jiafu An; Jiandong Chen (Journal of Cleaner Production, 2025)

Prediction of the potential dispersal corridors for Gaoligong hoolock gibbon in northern Yingjiang, Yunnan, China - Yong-liang Zhu; Meng-ling Xu; Li-xiang Zhang; Peng Li; Bao Jin; An-ru Zuo; Xue-long Jiang; Zhen-hua Guan (Journal for Nature Conservation, 2025)

Fast complete reduction of chlorite to chloride from drinking water in Al(III)/sulfite system: Kinetics, mechanisms, and applications - Xingli Ji; Li-an Hou; Shuili Yu; Ying Xu; Menghong Gao; Wei Zhang; Qian Xiao (Chemical Engineering Journal, 2025)

Mechanistic insights into the impact of calcium and magnesium ions on ferrous sulfide aggregation and reducing activity - Kaipian Shi; Li Yin; Junfeng An; Lin Xu; Chunqing Peng; Yong Zhang; Yuechun Zeng; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing” [Carbohydr. Polym. 343 (2024) 122492 - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2025)

Using chondroitin sulfate lithium hydrogel for diabetic bone regeneration via regulation of macrophage polarization - Chenci Xu; Weiqi Li; Jing Mao; Ziyang Liu; An Lao; Lixia Mao; Anqi Gu; Jiaqing Wu; Aili Shen; Kaili Lin; Jiaqiang Liu (Carbohydrate Polymers, 2025)

The impacts of yaw attitude strategies for eclipsing GNSS satellites on precise point positioning time transfer - Lei Wang; Wenbin Shen; Lihong Li; An Ning; Kuangchao Wu; Wei Xu; Ziyu Shen (GPS Solutions, 2025)

Organic matter determines the exchange of nutrients at sediment-water interface in coastal bays - Jiasen Zhong; Ehui Tan; Chunwei Fu; Guiyi Ma; Yongkai Chang; Zhixiong Huang; Jingchao Yin; Fengying Li; Jianzhong Su; Min Xu; Zhenzhen Zheng; Jian’an Liu; et al. (Acta Oceanologica Sinica, 2025)

Remediation of Cd-As-Ni co-contaminated soil by extracellular polymeric substances from Bacillus subtilis: Dynamic improvements of soil properties and ecotoxicity - Yang Li; Lei Cheng; Baolin Yang; Yanan Zhao; Yuting Ding; Chenxi Zhou; Yuanyuan Wu; Ruoyun Dong; Yun Liu; An Xu (Science of The Total Environment, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

Reproductive and germ-cell mutagenic effects of poly-and perfluoroalkyl substances (PFAS) to Caenorhabditis elegans after multigenerational exposure - Zhenxiao Cao; Linglong Dai; Jiali Li; Jingyi Zhang; Xialian Wang; An Xu; Hua Du (Science of The Total Environment, 2024)

Degradation of dyeing wastewater by sodium persulfate activated with Fe@MXene - Dawu Shu; Wanxin Li; Shaolei Cao; Bo Han; Chengshu Xu; Fangfang An (Journal of Environmental Chemical Engineering, 2024)

Hierarchical nanoarchitectonics of hollow hexanitrostilbene (HNS) microspheres to improve safety and combustion performance - Yi Liu; Jiani Xie; Yunyan Guo; Jiawei Li; Kai Han; Linchong Xu; Chongwei An; Zhongliang Ma; Bidong Wu (Fuel, 2024)

Corrigendum to “A critical review on graphene oxide membrane for industrial wastewater treatment” [Environ. Res. 223 (2023) 115409] - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2024)

Association between phthalates exposure and all-cause mortality among diabetic cases: A prospective study - Xu Cheng; Shiyang Zhang; Jun An; Chengyong Jia; Xin Zhang; Peiwen Li; Youbing Guan; Yan Yan; Zhuoya Zhao; Yuenan Liu; Tao Jing; Suli Huang; et al. (Environmental Pollution, 2024)

Butterfly wing-inspired superhydrophobic photonic cellulose nanocrystal films for vapor sensors and asymmetric actuators - Bang An; Mingcong Xu; Wenye Sun; Chunhui Ma; Sha Luo; Jian Li; Shouxin Liu; Wei Li (Carbohydrate Polymers, 2024)

High-level extracellular expression of phospholipase D by combinatorial fine-tuning strategy in Bacillus subtilis for efficient biosynthesis of phosphatidic acid - Peng Zhang; Xin-An Mao; Jin-Song Gong; Xiao-Li Kong; Chang Su; Xiao-Mei Zhang; Zhi-Ming Rao; Zheng-Hong Xu; Jin-Song Shi (Bioresource Technology, 2024)

Genotype–phenotype correlation study of structural abnormalities in a fetal brain caused by a novel KDM4B variant - Xuliang Zhao; Xu Li; Min Yu; Jian-an Jia; Ruixia Tian; Fuxi Zhu (Molecular Biology Reports, 2024)

Probabilistic quantile multiple fourier feature network for lake temperature forecasting: incorporating pinball loss for uncertainty estimation - Siyuan Liu; Jiaxin Deng; Jin Yuan; Weide Li; Xi’an Li; Jing Xu; Shaotong Zhang; Jinran Wu; You-Gan Wang (Earth Science Informatics, 2024)
Lake temperature forecasting is crucial for understanding and mitigating climate change impacts on aquatic ecosystems. The meteorological time series data and their relationship have a high degree of complexity and uncertainty, making it difficult to predict lake temperatures. In this study, we propose a novel approach, Probabilistic Quantile Multiple Fourier Feature Network (QMFFNet), for accurate lake temperature prediction in Qinghai Lake. Utilizing only time series data, our model offers practical and efficient forecasting without the need for additional variables. Our approach integrates quantile loss instead of L2-Norm, enabling probabilistic temperature forecasts as probability distributions. This unique feature quantifies uncertainty, aiding decision-making and risk assessment. Extensive experiments demonstrate the method’s superiority over conventional models, enhancing predictive accuracy and providing reliable uncertainty estimates. This makes our approach a powerful tool for climate research and ecological management in lake temperature forecasting. Innovations in probabilistic forecasting and uncertainty estimation contribute to better climate impact understanding and adaptation in Qinghai Lake and global aquatic systems.

A highly specific two-photon fluorescent probe for real-time monitoring of acetylcholinesterase in neurogenic disorders in vivo - Weizhen An; Zhongxi Huang; Wei Jiang; Fangning Du; Chenfeng Xu; Qian Shen; Naidi Yang; Jia Zhou; Lin Li; Changmin Yu (Analytica Chimica Acta, 2024)

The Complete Mitochondrial Genome of Chilo infuscatellus (Lepidoptera: Pyralidae), and Related Phylogenetic Analysis - Jiequn Yi; Jianbai Liu; Yongkai Mao; Yinjie Cheng; Minjiang Lin; Hanliang Xu; Yuxing An; Jihu Li; Han Wu (Biochemical Genetics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Enhancement of protective efficacy of recombinant attenuated Salmonella typhimurium delivering H9N2 avian influenza virus hemagglutinins(HA) antigen vaccine candidate strains by C-C motif chemokine ligand 5 in chickens(chCCL5) - Jingwen Ma; Shunshun Xu; Zewei Li; Yu-An Li; Shifeng Wang; Huoying Shi (Veterinary Microbiology, 2024)

Black sesame seeds: Nutritional value, health benefits, and food industrial applications - Zhenxia Xu; Min Li; Nanjie Jiang; Changqing Gui; Yunhai Wang; Yuting An; Xia Xiang; Qianchun Deng (Trends in Food Science & Technology, 2024)

Divergent accumulation of microbial necromass and plant lignin phenol induced by adding maize straw to fertilized soils - Xu Liu; Roland Bol; Tingting An; Yaocen Liu; Yingde Xu; Shuangyi Li; Jingkuan Wang (Soil and Tillage Research, 2024)

Long-term exposure to low-level ozone and the risk of hypertension: A prospective cohort study conducted in a low-pollution region of southwestern China - Fuyan Zhang; Ziyun Wang; Ling Li; Xu Su; Yuandong Hu; Yu Du; Qingqing Zhan; Tianlin Zhang; Qinyu An; Tao Liu; Yanli Wu (Science of The Total Environment, 2024)

Early anomaly detection of wind turbine gearbox based on SLFormer neural network - Zekun Wang; Xue Jiang; Zifei Xu; Chang Cai; Xiaodong Wang; Jianzhong Xu; Xiaohui Zhong; Wei Yang; Qing 'an Li (Ocean Engineering, 2024)

Corrigendum to “Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the industrial revolution recorded by high-resolution stalagmites” [Global and Planetary Chang, 232 (2024) 104337] - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Genomic analysis of hypoxia-tolerant population of the Chinese mitten crab (Eriocheir sinensis) - Feng-yuan Yan; Yuan-feng Xu; Wen-rong Feng; Qing-hong He; Guo-an Hua; Wen-jing Li; Pao Xu; Jun Zhou; Yong-kai Tang (Fish & Shellfish Immunology, 2024)

Continuous measurement of the dynamics of residential indoor and outdoor NO2 and the contributions to human exposure - Jianwei Gu; Xu Du; Qiaoqiao Wang; Zhishu Liang; Guiying Li; Taicheng An (Environmental Pollution, 2024)

Design of graphitic multichannel monolith electrode with in-situ transformed Ni-N-C sites for continuous electrolysis of CO2 - Xu Hu; Hong-Liang Xu; Ling-Yu Dong; Wen-Cui Li; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

LNP-mRNA delivers TNF-α antibody to deep cartilage and protects against osteoarthritis - Baixing Li; Lei Cui; Keyu Kong; Yichuan Pang; Yan Chen; Shuning Zhang; Fangfang Wang; Tangjun Zhou; Yunfeng Hua; Mi Cao; Hongtao Xu; An Qin; et al. (Chemical Engineering Journal, 2024)

Constructing asymmetric-electron-density Pd-Zn dual-atoms on N-doped defective mesoporous carbon for electrochemical reduction of CO2 - Yanlong Gong; Xiaohong Yang; Ying Zhang; Jingyun Li; Liang Xu; Song Li; Haitao Fu; Xizhong An (Chemical Engineering Journal, 2024)

Influence of silicates on the stability and reduction of ferrous sulfide in water - Kaipian Shi; JunFeng An; Li Yin; Juan Wang; Ying Xu; Desheng Kong; Yong Zhang; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Chemical Engineering Journal, 2024)

Chitosan/rutin multifunctional hydrogel with tunable adhesion, anti-inflammatory and antibacterial properties for skin wound healing - Ran An; Chenyu Shi; Yan Tang; Zan Cui; Yinping Li; Zhiyong Chen; Min Xiao; Li Xu (Carbohydrate Polymers, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Associations between polychlorinated biphenyls and cancer risk among type 2 diabetes: The modifying effects of lifestyle - Peiwen Li; Yu Wang; Qianying Liu; Yan Yan; Zhuoya Zhao; Shiyang Zhang; Chengyong Jia; Jun An; Cheng Xu; Xin Zhang; Tao Jing; Huan Guo; et al. (Chemosphere, 2024)

Mitigation of hypoxia and ocean acidification on the inner East China Sea shelf impacted by the 2023 summer drought - Shiping Lei; Dezhi Bu; Xianghui Guo; Yi Xu; Yi Yang; Shuqi An; Yan Li; Jinyan Pang; Kuanbo Zhou (Marine Pollution Bulletin, 2024)

Crustal configuration beneath the Santos and Campos Basins, southeastern Brazil: A refined Moho depth model based on gravity and seismic data in spherical coordinates - Wenqiang Xu; Changli Yao; Xianzhe Yin; Li Xiong; Junlu Wang; Shaole An; Guangxi Chen (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Dicranopteris pedata improves soil quality by enhancing nutrient deposition, decreasing metal concentration, and boosting microbial diversity on abandoned rare earth elements mining sites - Xi-Wen Cui; Zhen-An Xu; Xian Chen; Zhi-Biao Chen; Jia-Bing Li; Rong-Rong Xie; Hong Zhang; Yong Zhang; Yong-He Han (Journal of Environmental Chemical Engineering, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Impact of biochar synergized bacteria on Mn2+ and NH4+-N removal and CO2 immobilization in water by enhanced extracellular electron transfer - Shuman Deng; Qiang An; Weifeng Zhang; Zheng Li; Jiali Song; Yichen Yang; Bohan Xu; Binbin Ran; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

The toxicity of cisplatin derives from effects on renal organic ion transporters expression and serum endogenous substance levels - Mingkang Zhang; Yile Li; Yanrong Ma; Yongwen Jin; Xueyan Gou; Yufan Yuan; Fen Xu; Xin'an Wu (Food and Chemical Toxicology, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Relative dating of fault activity using the principle of cross-cutting relationships: An automated approach - An-Bo Li; Shi-Yu Xu; Xian-Yu Liu; Guo-Nian Lü; Xian-Li Xie; Matthew Fox (Computers & Geosciences, 2024)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Altering electronic states of Cu sites in Covalent organic frameworks for synthesis of formate via CO2 reduction - Xiubei Yang; Xuewen Li; Qizheng An; Shuang Zheng; Guojuan Liu; Shuai Yang; Qing Xu; Gaofeng Zeng (Chemical Engineering Journal, 2024)

Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2024)

Different variations in PM2.5 sources and their specific health risks in different periods in a heavily polluted area of the Beijing-Tianjin-Hebei region of China - Jiwei Li; Lihong Ren; Yunfei Wu; Renjian Zhang; Xiaoyang Yang; Gang Li; Erhao Gao; Jiutao An; Yisheng Xu (Atmospheric Research, 2024)

Refractory COD removal from bio-treated paper wastewater using powdered activated coke adsorption technology with ozonation regeneration: Performance and molecular insights - Ying An; Huimin Zhang; Li Fu; Chen Tang; Mengyu Wang; Yunxin Xing; Fuqiang Xu; Xiao Sun; Zhen Zhou (Chemosphere, 2024)

Integrated tea polyphenols and polydopamine functionalized graphene anode for improved bioelectricity generation and Cr(VI) reduction in microbial fuel cells - Deliang Guo; Xinru Wang; Qikai Fu; Ling Li; Runze Li; Xiaolin Xu; Xiongfang An (Chemosphere, 2024)

High-risk ARGs (HRA) Chip: A high-throughput qPCR-based array for assessment of high-risk ARGs from the environment - Huan-Qin Li; Mei-Rong Xu; Xin-Li An; Hu Liao; Li-Juan Li; Wei Li; Jian-Qiang Su (Water Research, 2024)

Electro-oxidation of 5-hydroxymethylfurfural in a low-concentrated alkaline electrolyte by enhancing hydroxyl adsorption over a single-atom supported catalyst - Xiaoxia Xia; Jingyi Xu; Xinru Yu; Jing Yang; An-Zhen Li; Kaiyue Ji; Lei Li; Min Ma; Qian Shao; Ruixiang Ge; Haohong Duan (Science Bulletin, 2024)

Experimental and numerical study on effects of different excitations and liquid levels on sloshing in a large-scale LNG tank - Zhanxue Cao; Mi-An Xue; Guohui Xu; Xiaoli Yuan; Zhanghan Ye; Longsheng Li; Jinhai Zheng; Jisheng Zhang (Ocean Engineering, 2024)

Blood trihalomethane and urinary haloacetic acid concentrations in relation to hypertension: An observational study among 1162 healthy men - Guangming Li; Shiyu Xu; Carmen Messerlian; Yu Zhang; Ying-Jun Chen; Yang Sun; Vicente Mustieles; Yi Wang; An Pan; Chong Liu; Yi-Xin Wang (Journal of Hazardous Materials, 2024)

Indirect photodegradation of typical pyrrolizidine alkaloids in water induced by triplet states of dissolved organic matter - Menghong Gao; Shuili Yu; Rongsheng Ning; Xingli Ji; Ying Xu; Li’an Hou (Journal of Hazardous Materials, 2024)

Treadmill Exercise Reshapes Cortical Astrocytic and Neuronal Activity to Improve Motor Learning Deficits Under Chronic Alcohol Exposure - Linglin Liu; Lanzhi Luo; Ji-an Wei; Xintong Xu; Kwok-Fai So; Li Zhang (Neuroscience Bulletin, 2024)
Alcohol abuse induces various neurological disorders including motor learning deficits, possibly by affecting neuronal and astrocytic activity. Physical exercise is one effective approach to remediate synaptic loss and motor deficits as shown by our previous works. In this study, we unrevealed the role of exercise training in the recovery of cortical neuronal and astrocytic functions. Using a chronic alcohol injection mouse model, we found the hyperreactivity of astrocytes along with dendritic spine loss plus lower neuronal activity in the primary motor cortex. Persistent treadmill exercise training, on the other hand, improved neural spine formation and inhibited reactive astrocytes, alleviating motor learning deficits induced by alcohol exposure. These data collectively support the potency of endurance exercise in the rehabilitation of motor functions under alcohol abuse.

Simulation study of the rupture mechanism of through-cracking under freeze–thaw load coupling effect - Ying Xu; Zhongwen Wang; Meilu Yu; Haotian Xie; Yanghaonan Jiao; Qi An; Chengjie Li (Natural Hazards, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

Zinc oxide/graphene oxide nanocomposites specifically remediated Cd-contaminated soil via reduction of bioavailability and ecotoxicity of Cd - Yang Li; Lei Cheng; Baolin Yang; Yuting Ding; Yanan Zhao; Yuanyuan Wu; Yaguang Nie; Yun Liu; An Xu (Science of The Total Environment, 2024)

Differences in anodizing of two copper-containing coordination compounds by different degradation factors: Experiments and DFT calculations - Haodong Bi; Xu Zhao; Dandan Xu; Jianli Liu; Zhenglei He; Lihui An; Bo Zhu; Chang Sun; Zhengxin Li (Journal of Cleaner Production, 2024)

Unveiling damage mechanisms of SiC fiber-reinforced titanium matrix composites through ultrasonic scratching - Liyu Wang; Songmei Yuan; Xiaoxing Gao; Qilin Li; Weiwei Xu; Wenzhao An; Yang Luo; Bochuan Chen (Journal of Cleaner Production, 2024)

Characterization, hazard identification, and risk assessment of volatile organic compounds in Poly(butylene adipate-co-terephthalate)-based food contact articles - Hanke Li; Hongjian Miao; Lichang Chen; Qi-Zhi Su; Zhenwei Liu; Canghao Xie; Jinxin Liang; Siliang Wu; An-Qi Cui; Can Xu; Ben Dong; Dan Li; et al. (Food and Chemical Toxicology, 2024)

Parotid Gland Segmentation Using Purely Transformer-Based U-Shaped Network and Multimodal MRI - Zi’an Xu; Yin Dai; Fayu Liu; Siqi Li; Sheng Liu; Lifu Shi; Jun Fu (Annals of Biomedical Engineering, 2024)

Two new benzophenones from the moss Pogonatum spinulosum - Wen-Bin Duan; An-tang Peng; Shi-Nong Yuan; Shao-Nan Wang; Bo-Wen Li; Xu-Hong Duan (Natural Product Research, 2024)

Absorption, distribution, metabolism, and elimination of epoxiconazole enantiomers in lizards (Eremias argus) - Qiong An; Weiyu Hao; Zheng Ma; Leisen Zhang; Zheyuan Song; Bin Wan; Peng Xu; Huili Wang; Jing Chang; Jianzhong Li (Chemosphere, 2024)

Associations of multiple hydroxy-polycyclic aromatic hydrocarbons with serum levels of lipids in the workers from coking and non-ferrous smelting industries - Hang Yu; Li Chen; Dongming Chen; Yanpeng Gao; Guiying Li; Xiantao Shen; Shunqing Xu; Taicheng An (Journal of Hazardous Materials, 2024)

Effect of Lactobacillus fermentation on the structural feature, physicochemical property, and bioactivity of plant and fungal polysaccharides: A review - Zichao Wang; Yi Zheng; Xueyan Zhou; Xueqin Wang; Xirui Liu; Qiong Wang; Renyong Zhao; Minjie Gao; Zhitao Li; Yingjie Feng; Yongming Xu; Na Li; et al. (Trends in Food Science & Technology, 2024)

Long-term species-level observations indicate the critical role of soil moisture in regulating China's grassland productivity relative to phenological and climatic factors - Shuai An; Xiaoqiu Chen; Fangjun Li; Xuhui Wang; Miaogen Shen; Xiangzhong Luo; Shilong Ren; Hongfang Zhao; Yan Li; Lin Xu (Science of The Total Environment, 2024)

Treatment of emerging pyrrolizidine alkaloids in drinking water by UV/persulfate process: Kinetics, energy efficiency and degradation pathway - Menghong Gao; Shuili Yu; Li'an Hou; Xingli Ji; Rongsheng Ning; Ying Xu; Lei Li (Chemical Engineering Journal, 2024)

Identification of candidate genes for Fusarium head blight resistance from QTLs using RIL population in wheat - Mingxia Zhang; Peng Jiang; Qun Wu; Xu Han; Junxia Man; Junsheng Sun; Jinlong Liang; Jingchuan Chen; Qi Zhao; Ying Guo; Yanrong An; Haiyan Jia; et al. (Plant Molecular Biology, 2024)

Overexpression of Lias Gene Alleviates Cadmium-Induced Kidney Injury in Mice Involving Multiple Effects: Metabolism, Oxidative Stress, and Inflammation - Guangcui Xu; Weibing Li; Yingzheng Zhao; Ting Fan; Qiyu Gao; Yongbin Wang; Fengquan Zhang; Mingjing Gao; Zhen An; Zijiang Yang (Biological Trace Element Research, 2024)

H6N2 reassortant avian influenza virus isolate in wild birds in Jiangxi Province, China - Yingjie Wang; Xiang Li; Xinru Lv; Yi Li; Qing An; Yang Xiu; Xiangtong Lv; Haozhuo Song; Changyu Zhou; Qiushi Xu; Dan Qiao; Siyuan Yang; et al. (Virus Genes, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Brittle sedimentary strata focus a multimodal depth distribution of seismicity during hydraulic fracturing in the Sichuan Basin, Southwest China - Mengke An; Derek Elsworth; Fengshou Zhang; Rui Huang; Junlun Li; Zhengyu Xu; Zhen Zhong; Manchao He (Tectonophysics, 2024)

Shifts in C-degradation genes and microbial metabolic activity with vegetation types affected the surface soil organic carbon pool - Qian Huang; Baorong Wang; Jikai Shen; Fengjing Xu; Na Li; Penghui Jia; Yongjian Jia; Shaoshan An; Isaac Dennis Amoah; Yimei Huang (Soil Biology and Biochemistry, 2024)

Estimation of soil water storage according to its multi-scale correlations with environmental factors - Xuezhang Li; Ming’an Shao; Wei Hu; Xianli Xu; Kelin Wang (Soil and Tillage Research, 2024)

Photo-transformation of graphitic carbon nitride synthesized from different precursors: Influence on environmental fate and photocatalytic water disinfection - Shi’en Lei; Wanjun Wang; Chao Wang; Weixuan Li; Zhe Xu; Guiying Li; Taicheng An (Journal of Water Process Engineering, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

Sustained oxidation of Tea-Fe(III)/H2O2 simultaneously achieves sludge reduction and carbamazepine removal: The crucial role of EPS regulation - Wei Lin; Renglu Chen; Chuangxin Gong; Peter Desmond; Xu He; Jun Nan; Guibai Li; Jun Ma; An Ding; Huu Hao Ngo (Journal of Hazardous Materials, 2024)

Adaptive prediction for effluent quality of wastewater treatment plant: Improvement with a dual-stage attention-based LSTM network - Tong An; Kuanliang Feng; Peijin Cheng; Ruojia Li; Zihao Zhao; Xiangyang Xu; Liang Zhu (Journal of Environmental Management, 2024)

Soluble carbon source recovery using preconditioning coagulants for applicable short-term fermentation of waste activated sludge in WWTPs - Chang-An Huan; Qiandi Wang; Xiqi Li; Cong Du; Qingjie Meng; Xu Kang; Wenzong Liu (Environmental Research, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

BDTX-189, a novel tyrosine kinase inhibitor, inhibits cell activity via ERK and AKT pathways in the EGFR C797S triple mutant cells - Rui Wang; Wenrui Cui; Lanxin Li; Xiangkai Wei; Chunhong Chu; Guoliang Zhang; Chenxue Liu; Huixia Xu; Chenyang Liu; Ke Wang; Yanming Li; Lei An (Chemico-Biological Interactions, 2024)

Fungal necromass carbon contributes to organic carbon sequestration within soil macroaggregates under manure application combined with plastic film mulching - Xu Liu; Roland Bol; Tingting An; Yingde Xu; Chang Peng; Shuangyi Li; Jingkuan Wang (Journal of Soils and Sediments, 2024)

How does cultural distance affect tourism destination choice? Evidence from the correlation between regional culture and tourism flow - Zihan Li; Haiping Zhang; Yushu Xu; Tianyao Fang; Haoran Wang; Guo’An Tang (Applied Geography, 2024)

Genetic variation in the BLM gene and its expression in the ovaries is closely related to kidding number in goats - Dongwei An; Xiang Chen; Ziyang Li; Lingang Dai; Jiajin Huang; Meimei Xiao; Huan Liu; Jiali Xu; Yong Ruan (Theriogenology, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Associations of arsenic exposure and arsenic metabolism with the risk of non-alcoholic fatty liver disease - Yuenan Liu; Weiya Li; Jiazhen Zhang; Yan Yan; Qihang Zhou; Qianying Liu; Youbin Guan; Zhuoya Zhao; Jun An; Xu Cheng; Meian He (International Journal of Hygiene and Environmental Health, 2024)

Energy release behavior of Zr/B/KNO3 dual-fuel energetic composites: Powders and sticks - Chenyang Li; Chuanhao Xu; Haoyu Song; Xuan Zhan; Baoyun Ye; Jingyu Wang; Chongwei An (Fuel, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Aminated lignin-derived sponge carbon for the capacitive deionization of copper ions - Jiajia An; Chunping Li; Qiang Wang; Xiaosong Zhang; Daquan Zhang; Xingtao Xu; Likui Feng; Yijie Cheng (Desalination, 2024)

Ion-engineered solar desalination: Enhancing salt resistance and activated water yield - Haoxiang Guo; Peng Yan; Xuhui Sun; Jiangnan Song; Fengbo Zhu; Xiaoyu Guan; Swellam W. Sharshir; Junwen Shi; Zhengtong Li; Xingtao Xu; Meng An (Chemical Engineering Journal, 2024)

Atomically dispersed Fe-N-C catalyst with densely exposed Fe-N4 active sites for enhanced oxygen reduction reaction - Xiangyu Lu; Yaqiang Li; Peixia Yang; Yongbiao Wan; Dan Wang; Hao Xu; Lilai Liu; Lihui Xiao; Ruopeng Li; Guangzhao Wang; Jinqiu Zhang; Maozhong An; et al. (Chemical Engineering Journal, 2024)

Enhanced alkaline hydrogen evolution performance through Ru-Incorporated electronic structure Modification: Transitioning from Mo3P to Mo2RuP - Peng Zhang; Shiyu Xu; Zhengyang Li; Zongfu An; Ho Seok Park; Ji Man Kim; Pil J. Yoo (Chemical Engineering Journal, 2024)

Suppression of neutrophil extracellular traps is responsible for the amelioration of chemotherapeutic intestinal injury by the natural compound PEITC - Mei Bai; Shuaifei Li; Cui Zhang; Ning An; Jie Wang; Jia Qin; Rumeng Jia; Wentao Liu; Jingcai Cheng; Xuefeng Wu; Qiang Xu (Toxicology and Applied Pharmacology, 2024)

Global hidden spillover effects among concurrent green initiatives - Li An; Jianguo Liu; Qi Zhang; Conghe Song; Driss Ezzine-de-Blas; Jie Dai; Huijie Zhang; Rebecca Lewison; Eve Bohnett; Douglas Stow; Weihua Xu; Brett A. Bryan (Science of The Total Environment, 2024)

Removal of sulfonamide antibiotics by non-free radical dominated peroxymonosulfate oxidation catalyzed by cobalt-doped sulfur-containing biochar from sludge - Chen Wang; Yuanyuan Li; Yukun Wang; Yan Zhang; Jingbo Feng; Xiaomeng An; Rui Wang; Yinyin Xu; Xiuwen Cheng (Journal of Hazardous Materials, 2024)

New insights into the typical nitrogen-containing heterocyclic compound-quinoline degradation and detoxification by microbial consortium: Integrated pathways, meta-transcriptomic analysis and toxicological evaluation - Xuejiao An; Ningjian Li; Lizhen Zhang; Zihang Xu; Shulin Zhang; Qinghua Zhang (Journal of Hazardous Materials, 2024)

ASAP-MS combined with mass spectrum similarity and binary code for rapid and intelligent authentication of 78 edible flowers - Qian Meng; Jianqing Zhang; Xiaolan Li; Yun Li; Xuanjing Shen; Ziqing Li; Meng Xu; Changliang Yao; Pengfei Chu; Ya-Jun Cui; De-an Guo (Food Chemistry, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

Netrin1-carrying magnetic microspheres with magnetic field activate neurotrophin factors to guide neuronal outgrowth in vitro and in vivo - Meili Liu; Zitong An; Junwei Xu; Xiaomeng Deng; Yuchen Xiao; Ruhan A; Yeqiu Zhan; Chaojuan Yang; Ping Li; Yubo Fan (Chemical Engineering Journal, 2024)

Mimosa inspired intelligent anti-corrosive composite coating by incorporating lignin and pyridine derivatives grafted graphene oxide - Chang-An Xu; Xingchi Li; Zhengbang Tong; Zhuangzhuang Chu; Heng Fang; Yang Hu; Xudong Chen; Zhuohong Yang (Chemical Engineering Journal, 2024)

Physiology, microcystin production, and transcriptomic responses of Microcystis aeruginosa exposed to calcium and magnesium - Li Yin; Lin Xu; Kaipian Shi; Weiyu Chen; Yong Zhang; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Science of The Total Environment, 2024)

A novel antimony metallochaperone AntC in Comamonas testosteroni JL40 and its application in antimony immobilization - Lijin An; Mingzhu Xu; Mengjuan Hong; Lipeng Zhao; Ao Wei; Xiong Luo; Kaixiang Shi; Shixue Zheng; Mingshun Li (Science of The Total Environment, 2024)

Enhanced activation of persulfate by modified red mud biochar for degradation of dye pollutant: Resource utilization and non-radical activation - Zheng Li; Shuman Deng; Qiang An; Bin Zhao; Zihao Yang; Bohan Xu; Weifeng Zhang (Journal of Environmental Management, 2024)

Three-dimensional surface deformation from multi-track InSAR and oil reservoir characterization: A case study in the Liaohe Oilfield, northeast China - Wei Tang; Zhiqiang Gong; Xiubo Sun; Yu'an Liu; Mahdi Motagh; Zhicai Li; Jing Li; Agnieszka Malinowska; Jinbao Jiang; Lianhuan Wei; Xin Zhang; Xing Wei; et al. (International Journal of Rock Mechanics and Mining Sciences, 2024)

Monazite and zircon U Pb and muscovite 40Ar/39Ar geochronology constraints on the timing of magmatism and mineralization in the Huxingshan tungsten deposit, South China - Lei Zhu; Bin Li; An-Huai Lu; De-Xian Zhang; Jun-Wei Xu (Geochemistry, 2024)

Correlation investigation between core microbe inoculation and the evolution of flavor characteristics during the storage of sturgeon caviar (Acipenser gueldenstaedtii) - Li Liu; Shixue Lu; Weijia Zhang; Fan Bai; Jinlin Wang; Xuqing Zhang; He Xu; Xiaoming Jiang; Shucai An; Wei Li; Yuanhui Zhao; Xinxing Xu (Food Research International, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Structural and functional analysis of transforming growth factor beta regulator 1 (TBRG1) in the red swamp crayfish Procambarus clarkii: The initial insight into TBRG1's role in invertebrate immunity - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

Circulating Lipoproteins Mediate the Association Between Cardiovascular Risk Factors and Cognitive Decline: A Community-Based Cohort Study - Jialin Li; Qingxia Huang; Yingzhe Wang; Mei Cui; Kelin Xu; Chen Suo; Zhenqiu Liu; Yanpeng An; Li Jin; Huiru Tang; Xingdong Chen; Yanfeng Jiang (Phenomics, 2024)

Fluctuating redox conditions accelerate the electron storage and transfer in magnetite and production of dark hydroxyl radicals - Dan Li; Jieyi Sun; Yibo Fu; Wentao Hong; Heli Wang; Qian Yang; Junhong Wu; Sen Yang; Jianhui Xu; Yunfei Zhang; Yirong Deng; Yin Zhong; et al. (Water Research, 2024)

V-ATPase E mediates Cry2Ab binding and toxicity in Helicoverpa armigera - Yuge Zhao; Pin Li; Xue Yao; Yuepu Li; Yu Tian; Guiying Xie; Zhongyuan Deng; Shuxia Xu; Jizhen Wei; Xianchun Li; Shiheng An (Pesticide Biochemistry and Physiology, 2024)

Diverse Late Triassic arc magmatism and porphyry Cu deposits in the southeastern Tibetan Plateau: Related to slab tear along a subducting passive margin? - Wan-Li Tang; Jian-Lin Chen; Tian-Nan Yang; An Yin; Ji-Feng Xu; Jiang-Bo Ren (Lithos, 2024)

Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the Industrial Revolution recorded by high-resolution stalagmites - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Endoplasmic reticulum stress exacerbates microplastics-induced toxicity in animal cells - Zhanhang Wang; Shujuan Liu; Zefang Cheng; Ganggang Xu; Fu Li; Qiqi Bu; Lei Zhang; Yuxuan Song; Xiaopeng An (Food Research International, 2024)

Mechanism of interaction between astaxanthin and soy protein fibrils: Effects on complexes structure, rheological properties and bioaccessibility - Ning Li; Yi-fan Cui; Yi-an Liu; Mengyue Zhang; Yi-cheng Wang; Jiahui Shi; Xibo Wang; Ning Xu; Qingshan Chen (Food Hydrocolloids, 2024)

MOF-derived amorphous molybdenum trioxide anchored on nitrogen-doped porous carbon by facile in situ annealing for efficient oxidative desulfurization - Xin An; Xiang Gao; Jie Yin; Lixian Xu; Beibei Zhang; Jing He; Hongping Li; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

High temperature exacerbates ozone-induced airway inflammation: Implication of airway microbiota and metabolites - Fei Xu; Qiong Wu; Yishu Yang; Ling Zhang; Zhen Yan; Huijun Li; Juan Li; Zhen An; Hui Wu; Jie Song; Weidong Wu (Science of The Total Environment, 2023)

Unraveling the potential-dependent structure evolution in CuO for electrocatalytic biomass valorization - Ye Wang; Ming Xu; Xi Wang; Ruixiang Ge; Yu-Quan Zhu; An-Zhen Li; Hua Zhou; Fengen Chen; Lirong Zheng; Haohong Duan (Science Bulletin, 2023)

Enhancement of tolerance against flonicamid in Solenopsis invicta (Hymenoptera: Formicidae) through overexpression of CYP6A14 - Tian-yi Zhang; Chang-wei Gong; Jian Pu; An-chun Peng; Xu-yang Li; Yu-meng Wang; Xue-gui Wang (Pesticide Biochemistry and Physiology, 2023)

Modification of the distribution of humic acid complexations by introducing microbubbles to membrane distillation process for effective membrane fouling alleviation - Xitong Wang; Pan Li; Yubing Ye; Chen'ao Xu; Yanling Liu; Enchao Li; Qing Xia; Li'an Hou; Shuili Yu (Journal of Environmental Management, 2023)

Efficient activation of peroxydisulfate by modified red mud biochar derived from waste corn straw for levofloxacin degradation: Efficiencies and mechanisms - Zihao Yang; Qiang An; Shuman Deng; Bohan Xu; Zheng Li; Shian Deng; Bin Zhao; Zhihong Ye (Journal of Environmental Chemical Engineering, 2023)

Acid-modified red mud biochar for the degradation of tetracycline: Synergistic effect of adsorption and nonradical activation - Bohan Xu; Qiang An; Shuman Deng; Zheng Li; Zihao Yang; Haoyu Wu; Zhihong Ye (Journal of Environmental Management, 2023)

Photocatalytic degradation of tetrabromobisphenol A by Z-scheme WO3/ZnIn2S4 heterojunction: Efficiency, mechanism and toxicity evaluation - Bin Xu; Zhiquan An; Minjie Li; Bihong Zhang; Liang-Hong Guo (Journal of Environmental Chemical Engineering, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

Microplastics released from disposable medical devices and their toxic responses in Caenorhabditis elegans. - Tong Zhou; Jiajie Wu; Xi Hu; Zhenxiao Cao; Baolin Yang; Yang Li; Yanan Zhao; Yuting Ding; Yun Liu; An Xu (Environmental Research, 2023)

In-situ generated elemental selenium nanograins cooperated with NiSe2 microspheres for significantly enhanced magnesium-storage performance - Changchun Hu; Lin Ran; Hou-an Zhang; Shuai Cui; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Streamflow forecasting method with a hybrid physical process-mathematical statistic - Sen Wang; Ping-an Zhong; Feilin Zhu; Bin Xu; Jieyu Li; Xinyuan Qian; Bin Wang (Stochastic Environmental Research and Risk Assessment, 2023)

Prognostic value of left ventricular systolic function on moderate aortic stenosis: the China-VHD study - Xianbao Liu; Qifeng Zhu; Qiong Liu; Haiyan Xu; Hanyi Dai; Yaoyao Zhou; Jun Chen; Stella Ng; Ye Lu; Yanyan Zhao; Zhe Li; Yongjian Wu; et al. (Science Bulletin, 2023)

A review on polyhydroxyalkanoates production from various organic waste streams: Feedstocks, strains, and production strategy - Xuemei Fu; Heng Xu; Qi Zhang; Jiaxing Xi; Huihui Zhang; Mingxia Zheng; Beidou Xi; Li'an Hou (Resources, Conservation and Recycling, 2023)

Circulating organochlorine pesticide levels, genetic predisposition and the risk of incident type 2 diabetes - Chengyong Jia; Shiyang Zhang; Xu Cheng; Peiwen Li; Jun An; Xin Zhang; Wending Li; Yali Xu; Handong Yang; Tao Jing; Huan Guo; Meian He (Environmental Pollution, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Significantly improved high-temperature capacitive performance in polymer dielectrics utilizing ultra-small carbon quantum dots with Coulomb-blockade effect - Hangchuan Cai; Rui Wang; Bin Gou; Jing Fu; Yujie Zhu; Hao Yang; Jiangang Zhou; Manxi Li; An Zhong; Daoming Zhang; Huasong Xu; Chunhui Bi; et al. (Chemical Engineering Journal, 2023)

Role of nitrogen dual reaction sites in N-doped graphene aerogels for synergistic sulfamethoxazole adsorption and peroxymonosulfate activation in Fenton-like process - Ning An; Shijing Li; Bentuo Xu; Linbo Qian; Yi Shen; Kun Wang; Xiangyu Li; Min Zhao; Xiangyong Zheng; Renlan Liu (Chemical Engineering Journal, 2023)

In-situ utilization of EPS improves the directional oxidation ability of Fe(III)/H2O2 and enhances sludge dewaterability - Wei Lin; Chuangxin Gong; Renglu Chen; Xu He; Jun Nan; Guibai Li; Huu Hao Ngo; An Ding (Chemical Engineering Journal, 2023)

Occurrence, distribution and risk assessment of polycyclic aromatic hydrocarbons in soils around main water source areas of Beijing, China - Bin Li; Liang Zhao; Sining Zhong; Rui An; Ruoqi Ma; Xuming Xu; Qian Chen (Environmental Geochemistry and Health, 2023)

Phosphoproteome reveals long-term potentiation deficit following treatment of ultra-low dose soman exposure in mice - Qi Long; Zhenpeng Zhang; Yuan Li; Yuxu Zhong; Hongyan Liu; Lei Chang; Ying Ying; Tao Zuo; Yong'an Wang; Ping Xu (Journal of Hazardous Materials, 2023)

Corrigendum to “Astaxanthin protected against the adverse effects induced by diesel exhaust particulate matter via improving membrane stability and anti-oxidative property” [J Hazard Mater 456 (2023) 131684] - Tong Wang; Ying Liu; Yemian Zhou; Qiao Liu; Qixing Zhang; Mengzi Sun; Meng Sun; Han Li; An Xu; Yun Liu (Journal of Hazardous Materials, 2023)

Lipid metabolic links between serum pyrethroid levels and the risk of incident type 2 diabetes: A mediation study in the prospective design - Chengyong Jia; Gaokun Qiu; Hao Wang; Shiyang Zhang; Jun An; Xu Cheng; Peiwen Li; Wending Li; Xin Zhang; Handong Yang; Kun Yang; Tao Jing; et al. (Journal of Hazardous Materials, 2023)

Graphene oxide modulation of lignin-derived porous nanosheets for efficient desalination - Jiajia An; Chunping Li; Daquan Zhang; Xingtao Xu (Journal of Environmental Chemical Engineering, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

New insights into the regulation mechanism of Pacific white shrimp (Litopenaeus vannamei) hepatopancreas under 4-nonylphenol exposure using transcriptome analysis - Pei-Hua Zheng; Yao-Peng Lu; Xiu-Xia Zhang; Ke-Er Luan; Ze-Long Zhang; Jia-Jun Li; Tong Xu; Jun-Tao Li; Jian-An Xian; Hui Guo; An-Li Wang (Fish & Shellfish Immunology, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

Pulmonary flora-modified diesel particulate matter induced lung injury via cGAS signaling pathway - Meng Sun; Tong Wang; Yemian Zhou; Qiao Liu; Mengzi Sun; Han Li; Yanan Zhao; Yun Liu; An Xu; Ying Liu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Selenium alleviates biological toxicity of thiamethoxam (TMX): Bioaccumulation of TMX, organ damage, and antioxidant response of red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wen-Bin Xu; Chen-Yang Lin; Bang-Ze Li; Miao-An Shu (Journal of Hazardous Materials, 2023)

Identification and functional analysis of cytosolic phospholipase A2 (cPLA2) from the red swamp crayfish Procambarus clarkii: The first evidence of cPLA2 involved in immunity in invertebrates - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2023)

Insight into wavelength-dependent UVA-LED/chlorine process for micropollutant degradation: Performance, mechanism, and effects of water matrix - Ge Zeng; Jiamin Mai; Linqian An; Cui Huang; Juan Li; Haiping Wang; Qiuhua Li; Jingxin Yang; Xiaolong Xu; Changyu Liu; Jianbo Jia; Tao Yang; et al. (Chemical Engineering Journal, 2023)

Treatment of Dyes Wastewater by the Catalytic Wet Persulfate Oxidation Process in Reactors Using Red Mud Combined with Biochar as Catalyst - Shuman Deng; Zheng Li; Qiang An; Meng Tang; Chenlu Liu; Zihao Yang; Bohan Xu; Bin Zhao (Water, Air, & Soil Pollution, 2023)

Will green technological progress help industrial collaborative agglomeration increase regional carbon productivity: evidence from Yangtze River Delta urban agglomerations - Weijun He; Yizhan Li; Xu Meng; Mengfei Song; Thomas Stephen Ramsey; Min An (Environment, Development and Sustainability, 2023)

Effects of whole grain intake on glycemic traits: A systematic review and meta-analysis of randomized controlled trials - Shixiang Li; Aizhen Zong; Ran An; Haiou Wang; Lina Liu; Jie Liu; Xiaofei Guo; Zhixiang Xu; Jing Wang; Duo Li; Fangling Du; Tongcheng Xu (Critical Reviews in Food Science and Nutrition, 2023)

The overlooked role of Cr(VI) in micropollutant degradation under solar light irradiation - Tao Yang; Cui Huang; Linqian An; Ge Zeng; Juan Li; Changyu Liu; Xiaolong Xu; Jianbo Jia; Jun Ma (Water Research, 2023)

Astaxanthin protected against the adverse effects induced by diesel exhaust particulate matter via improving membrane stability and anti-oxidative property - Tong Wang; Ying Liu; Yemian Zhou; Qiao Liu; Qixing Zhang; Mengzi Sun; Meng Sun; Han Li; An Xu; Yun Liu (Journal of Hazardous Materials, 2023)

Uranium uptake is mediated markedly by clathrin-mediated endocytosis and induce dose-dependent toxicity in HK-2 cells - Liqun Huang; Ge Sun; Wenli Xu; Shufang Li; Xiujun Qin; Quan An; Zhongwen Wang; Jianguo Li (Environmental Toxicology and Pharmacology, 2023)

Discrepancy of synaptic and microtubular protein phosphorylation in the hippocampus of APP/PS1 and MAPT×P301S transgenic mice at the early stage of Alzheimer’s disease - Qiyao Wang; Chenglong Xia; An Zhu; Yongjie Bao; Jiani Lu; Yuan Chen; Jiayi Xu; Binbin Wang; C. Benjamin Naman; Liping Li; Qinwen Wang; Hao Liu; et al. (Metabolic Brain Disease, 2023)

Highly oxygenated germacrane-type sesquiterpenoids from the whole plant of Salvia cavaleriei H.Lév. and their biological activities - Xiao-Han Chen; Xu Liu; Wen-Bo Cui; Feng-Li An; Li Liu; Qian Wu; Jian-Ning Yu; Jian-Ye Dai; Zhan-Xin Zhang; Dong-Qing Fei (Phytochemistry, 2023)

Water-solvent regulation on complete hydrolysis of thermosetting polyester and complete separation of degradation products - Wenli An; Xuehui Liu; Junyan Li; Xu Zhao; Yuwei Long; Shimei Xu; Yu-Zhong Wang (Journal of Hazardous Materials, 2023)

Valorization strategies for hazardous proteinaceous waste from rendering production – Recent advances in specified risk materials (SRMs) conversion - Tao Shui; An Li; Michael Chae; Chunbao Charles Xu; David C. Bressler (Journal of Hazardous Materials, 2023)

Association between polychlorinated biphenyls exposure and incident type 2 diabetes mellitus: A nested case-control study - Peiwen Li; Yali Xu; Zhaoyang Li; Xu Cheng; Chengyong Jia; Shiyang Zhang; Jun An; Xin Zhang; Yan Yan; Meian He (Environmental Research, 2023)

Repeated photocatalytic inactivation of E. coli by UV + Ni foam@TiO2: Performance and photocatalyst deactivation - Miao Wang; Zhe Xu; Zhenlian Qi; Yiwei Cai; Guiying Li; Wonyong Choi; Taicheng An (Chemical Engineering Journal, 2023)

Cation-deficient T-Nb2O5/graphene Hybrids synthesized via chemical oxidative etching of MXene for advanced lithium-ion capacitors - Lei Wang; Xiong Zhang; Chen Li; Yanan Xu; Yabin An; Wenjie Liu; Tao Hu; Sha Yi; Kai Wang; Xianzhong Sun; Yue Gong; Zhong-Shuai Wu; et al. (Chemical Engineering Journal, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

The catalytic oxidation process of atrazine by ozone microbubbles: Bubble formation, ozone mass transfer and hydroxyl radical generation - Ting Liu; Bin Zhang; Wenqian Li; Boda Li; Ziwen Han; Yanjie Zhang; An Ding; Shutao Wang; Jun Ma; Xu He (Chemosphere, 2023)

Corrigendum to ‘Co-occurrence network of microbial communities affected by application of anaerobic fermentation residues during phytoremediation of ionic rare earth tailings area’ [Sci. Total Environ. 856 (2023) 159223] - Liumeng Chen; Shasha Chen; Yi Zhang; Yun Long; Xiaoying Kong; Shujia Wang; Lianhua Li; Fei Wang; Yongmin Sun; An Xu (Science of The Total Environment, 2023)

Corrigendum to “Co-occurrence network of microbial communities affected by application of anaerobic fermentation residues during phytoremediation of ionic rare earth tailings area” [Sci. Total Environ. 856 (2023) 159223] - Liumeng Chen; Shasha Chen; Yi Zhang; Yun Long; Xiaoying Kong; Shujia Wang; Lianhua Li; Fei Wang; Yongmin Sun; An Xu (Science of The Total Environment, 2023)

Reconstruction of new high-performance epoxy thermoset based on the full utilization of the degradation products of waste epoxy thermoset - Xu Zhao; Xue Zhao; Wenli An; Yuwei Long; Xuehui Liu; Li Chen; Shimei Xu; Yu-Zhong Wang (Journal of Environmental Chemical Engineering, 2023)

Metabolomics profile of plasma in acute diquat-poisoned patients using gas chromatography-mass spectrometry - Xinhua Dai; Maozhu Liu; Shuyun Xu; Han Zhao; Xuezhi Li; Yangjuan Bai; Yuangao Zou; Yunfei An; Fei Fan; Jing Zhang; Bei Cai (Food and Chemical Toxicology, 2023)

A deep learning-based fully automatic and clinical-ready framework for regional myocardial segmentation and myocardial ischemia evaluation - Mujun An; Junhuan Li; Xiaoyang Xu; U. Joseph Schoepf; Rock H. Savage; Kunlin Cao; Qi Song; Zeying Wang; Zhi Liu; Yuwei Li; Pengfei Zhang (Medical & Biological Engineering & Computing, 2023)

Juvenile hormone regulates the photoperiodic plasticity of elytra coloration in the ladybird Harmonia axyridis - Jia‐Xu Li; Zhong Tian; Xing‐Feng Liu; Bei Li; Hao‐Min An; Colin S. Brent; Jia‐Lu Wang; Xiao‐Ping Wang; Wen Liu (Molecular Ecology, 2023)
Many animals, including insects, exhibit plasticity of body colour in response to environmental changes. Varied expression of carotenoids, major cuticle pigments, significantly contributes to body colour flexibility. However, the molecular mechanisms by which environmental cues regulate carotenoid expression remain largely unknown. In this study, we used the ladybird Harmonia axyridis as a model to investigate the photoperiodic‐responsive plasticity of elytra coloration and its endocrine regulation. It was found that H. axyridis females under long‐day conditions develop elytra that are much redder than those under short‐day conditions, resulting from the differential accumulation of carotenoids. Exogenous hormone application and RNAi‐mediated gene knockdown indicate that carotenoid deposition was directed through the juvenile hormone (JH) receptor‐mediated canonical pathway. Moreover, we characterized an SR‐BI/CD36 ( SCRB ) gene SCRB10 as the carotenoid transporter responding to JH signalling and regulating the elytra coloration plasticity. Taken together, we propose that JH signalling transcriptionally regulates the carotenoid transporter gene for the photoperiodic coloration plasticity of elytra in the beetles, which reveals a novel role of the endocrine system in the regulation of carotenoid‐associated animal body coloration under environmental stimuli.

Late Pleistocene to Holocene facies architecture and sedimentary evolution of the Zhejiang coast, East China Sea - Jian Liu; Jiandong Qiu; Yoshiki Saito; Xin Zhang; Hong Wang; Feifei Wang; Lilei Chen; Gang Xu; Bin Chen; Meina Li; Yuhui An (Marine Geology, 2023)

Root exudates increased arsenic mobility and altered microbial community in paddy soils - Ouyuan Jiang; Lvyao Li; Guilan Duan; Williamson Gustave; Weiwei Zhai; Lina Zou; Xia An; Xianjin Tang; Jianming Xu (Journal of Environmental Sciences, 2023)

Incorporation of probiotics into 3D printed Pickering emulsion gel stabilized by tea protein/xanthan gum - Dan Xu; Zhenbin Liu; Zinuo An; Liangbin Hu; Hongbo Li; Haizhen Mo; Subrota Hati (Food Chemistry, 2023)

Inducing the structural interplay of binary pulse protein complex to stimulate the solubilization of chickpea (Cicer arietinum L.) protein isolate - Yongxin Teng; Ting Zhang; Hongmin Dai; Yabin Wang; Jianteng Xu; Xin-An Zeng; Bin Li; Xiangwei Zhu (Food Chemistry, 2023)

Geochemical characteristics and behaviors of polycyclic aromatic hydrocarbons (PAHs) in soil, water, and sediment near a typical nonferrous smelter - Miao Li; Mingming Shi; Tianpeng Hu; Weijie Liu; Yao Mao; Yue Yu; Haikuo Yu; An Xu; Wencong Yang; Xinli Xing; Jiaquan Zhang; Shihua Qi (Journal of Soils and Sediments, 2023)

Stochastic multi-criteria decision making framework based on SMAA-VIKOR for reservoir flood control operation - Chengjing Xu; Ping-an Zhong; Feilin Zhu; Lingjie Li; Qingwen Lu; Luhua Yang (Hydrological Sciences Journal, 2023)

Euphorfinoids A and B, a pair of ent -atisane diterpenoid epimers from the roots of Euphorbia fischeriana, and their bioactivities - Jiang-Chun Wei; Yu-Ning Gao; Hui-Hui Huang; Xiao-Yu Zhang; Xuan-Li Liu; Xiao-Xu Gao; Na Li; Yue Zhao; An-Hua Wang; Jing-Ming Jia (Natural Product Research, 2023)

Retrieving leaf area index from FY-3D MERSI-II data using a sensor-adaptive algorithm - Yepei Chen; Pengfei Li; Chuan Xu; Zhina Song; Kaimin Sun; Wenzhuo Li; Xiuqing Hu; Qing An (International Journal of Remote Sensing, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Preparation of Pickering emulsion gel stabilized by tea residue protein/xanthan gum particles and its application in 3D printing - Zinuo An; Zhenbin Liu; Haizhen Mo; Liangbin Hu; Hongbo Li; Dan Xu; Bimal Chitrakar (Journal of Food Engineering, 2023)

Rapid hydrolysis of PET in high-concentration alcohol aqueous solution by pore formation and spontaneous separation of terephthalate - Xiong-Lei Wang; Wen-Li An; Rongcheng Du; Fei Tian; Yang Yang; Xu Zhao; Shimei Xu; Yu-Zhong Wang (Journal of Environmental Chemical Engineering, 2023)

The effect of clay type and solid wettability on bitumen extraction from Canadian oil sands - An Li; Rui Li; Ci Yan; Han Wang; Qingxia Liu; Jacob H. Masliyah; Hongbo Zeng; Zhenghe Xu (Fuel, 2023)

A critical review on graphene oxide membrane for industrial wastewater treatment - Ye-Chen An; Xiao-Xu Gao; Wen-Li Jiang; Jing-Long Han; Yuan Ye; Tian-Ming Chen; Rui-Yun Ren; Jia-Hui Zhang; Bin Liang; Zhi-Ling Li; Ai-Jie Wang; Nan-Qi Ren (Environmental Research, 2023)

Scale-specific controls of soil water storage along a transect in a semiarid catchment - Xuezhang Li; Xianli Xu; Ming'an Shao; Kelin Wang (European Journal of Agronomy, 2023)

Comparison and Investigation of Exosomes from Human Amniotic Fluid Stem Cells and Human Breast Milk in Alleviating Neonatal Necrotizing Enterocolitis - Xiaohan Hu; Rui Zhang; Hansi Liang; Jingnan An; Yuan Yang; Jie Huo; Zhenjiang Chen; Wei Quan; Lu Jiang; Cancan Li; Jian Li; Fang Li; et al. (Stem Cell Reviews and Reports, 2023)
In view of the devastating impact of neonatal necrotizing enterocolitis (NEC) on newborns, the research on its intervention is particularly important. Although exosomes from human amniotic fluid stem cells (AFSC) and human breast milk (HBM) can protect against NEC, their mechanisms remain unclear. Here, we intend to compare the intervention effects of two types of exosomes on NEC mouse model and reveal their respective regulatory mechanisms. In general, both AFSC-derived exosomes (AFSC-exos) and HBM-derived exosomes (HBM- exos) can alleviate NEC- associated intestinal injury, significantly reduce NEC score, and reduce systemic and ileal inflammation and NEC related brain injury during experimental NEC. However, the mode and mechanism of action of the two sources of exosomes were not identical. In vivo, the number of ileal crypts was more significantly restored after HBM-exos intervention than AFSC-exos, and in vitro, HBM-exos preferentially inhibited the inflammatory response of intestinal epithelial cells (IECs), whereas AFSC-exos preferentially regulated the migration of IECs. Mechanistically, GO and KEGG analyses revealed the different therapeutic mechanisms of AFSC-exos and HBM-exos in NEC. Taken together, our results illustrate that AFSC-exos and HBM-exos reduce the severity of experimental NEC and intestinal damage through different mechanisms, supporting the potential of cell-free or breast milk free exosome therapy for NEC. Graphical Abstract

Physiological and Cytological Analyses of the Thousand-Grain Weight in ‘Zhongyan96-3’ Wheat - Luhua Li; Shuai Yang; Zhongni Wang; Mingjian Ren; Chang An; Fumin Xiong; Yuxuan Chen; Ruhong Xu (Journal of Plant Growth Regulation, 2023)

Potential antiplatelet aggregation metabolites from the discarded sorghum ( Sorghum bicolor L.) root - Wan-ting Xu; Qiao An; Ling-hui Ruan; Fei Zhou; Lang Zhou; Mei Peng; Li-lang Li; Xiao-sheng Yang; Qi-ji Li; Juan Yang (Natural Product Research, 2023)

Occurrence, distribution and risk assessment of microplastics and polycyclic aromatic hydrocarbons in East lake, Hubei, China - Mingming Shi; Jiaxin Zhu; Tianpeng Hu; An Xu; Yao Mao; Li Liu; Yuan Zhang; Zhenbing She; Peng Li; Shihua Qi; Xinli Xing (Chemosphere, 2023)

Fish damage due to tubular turbine: Experiments and CFD simulations - Chunxia Yang; Qian Li; Ding'e Xu; Jiawei Wu; Yuan Zheng; Yuquan Zhang; An Yu (Ocean Engineering, 2023)

Enhanced delivery of remedial reagents in low-permeability aquifers through coupling with groundwater circulation well - Peng Wang; Jia Li; Pei An; Zheng Yan; Yang Xu; Shengyan Pu (Journal of Hydrology, 2023)

Sonocatalytic degradation of tetracycline by BiOBr/FeWO4 nanomaterials and enhancement of sonocatalytic effect - Liang Xu; Xue-Qian Wu; Chun-Yu Li; Ni-Ping Liu; Hui-Li An; Wan-Ting Ju; Wen Lu; Bin Liu; Xiao-Fang Wang; Yang Wang; Xin Wang (Journal of Cleaner Production, 2023)

Nanoemulsion: A novel delivery approach for thermosensitive IgG on inhibiting milk fat oxidation - An-Qi Zhang; Meng-Qi Liu; Xiao-Yan Li; Di Xu; Yu-Qi Yin; Nan-Nan Song; Ying-Hua Zhang (Food Research International, 2023)

Revisiting the centrality definition and observable centrality dependence of relativistic heavy-ion collisions in PACIAE model - Yu-Liang Yan; Dai-Mei Zhou; An-Ke Lei; Xiao-Mei Li; Xiao-Ming Zhang; Liang Zheng; Gang Chen; Xu Cai; Ben-Hao Sa (Computer Physics Communications, 2023)

The pollution characteristics, source identification and health risks of multiple classes atmospheric SVOCs with complex emission sources of the petrochemical plant and other industries - Jun Xiang; Rongfa Xu; Dongwei Du; Bin Tang; Miao Yi; Fengshan Cai; Xiao Yan; Jing Zheng; Guiying Li; Taicheng An (Atmospheric Environment, 2023)

The PER3rs772027021 SNP induces pigmentation phenotypes of dyschromatosis universalis hereditaria - Hongyu Chen; Pingping Yang; Dan Yang; Dongsheng Wang; Mao Lu; Yadong Li; Zhiqiang Zhong; Jing Zhang; Zhen Zeng; Zhi Liu; Xiaohua Zeng; Xu Jia; et al. (Journal of Molecular Medicine, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Ions play different roles in virus removal caused by different NOMs in UF process: Removal efficiency and mechanism analysis - Zixiao Ren; Haiyan Cao; Peter Desmond; Bingsheng Liu; Huu Hao Ngo; Xu He; Guibai Li; Jun Ma; An Ding (Chemosphere, 2023)

Evaluation of rice straw and its transformation products on norfloxacin degradation and antibiotic resistome attenuation during soil incorporation - Shaohua Tian; Xuecong Sun; Hai Xiao; Yanyan Zhou; Xu Huang; Xin-Li An; Chaoxiang Liu; Jian-Qiang Su (Chemosphere, 2023)

Comprehensive evaluation of novel fungicide benzovindiflupyr at the enantiomeric level: Bioactivity, toxicity, mechanism, and dissipation behavior - Xiaokang An; Xinglu Pan; Runan Li; Fengshou Dong; Wentao Zhu; Jun Xu; Xiaohu Wu; Yongquan Zheng (Science of The Total Environment, 2023)

Effects of microbial inoculum on microbial community and enzyme activity involved in nitrogen-sulfur metabolism during sewage sludge composting - Tingting Hou; Yujie Zhou; Xu Cao; Weiguang Li; Shumei Zhang; Yi Zhao; Li Chen; Qi An; Liqiang Meng (Science of The Total Environment, 2023)

Characterization of fibroblast growth factor receptor 4 (FGFR4) from the red swamp crayfish Procambarus clarkii and its role in antiviral and antimicrobial immune responses - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wen-Bin Xu; Wei-Ren Dong; Miao-An Shu (Journal of Invertebrate Pathology, 2023)

Damming has changed the migration process of microplastics and increased the pollution risk in the reservoirs in the Shaying River Basin - Jiachen Shen; Xu Gu; Run Liu; Hongyu Feng; Dianpeng Li; Yan Liu; Xufei Jiang; Ge Qin; Shuqing An; Ning Li; Xin Leng (Journal of Hazardous Materials, 2023)

Effect of β-glucosidase on the aroma of liquid-fermented black tea juice as an ingredient for tea-based beverages - Shuang Liang; Fang Wang; Daniel Granato; Xiaoyu Zhong; An-Feng Xiao; Qun Ye; Lijun Li; Chun Zou; Jun-Feng Yin; Yong-Quan Xu (Food Chemistry, 2023)

A hybrid method for optimization of frame structures with good constructability - An Xu; Shumin Li; Jiyang Fu; Anil Misra; Ruohong Zhao (Engineering Structures, 2023)

DNA Methylation Alterations and Their Association with High Temperature Tolerance in Rice Anthesis - Bo Li; Haiya Cai; Ke Liu; Bingzhuang An; Rong Wang; Fang Yang; Changli Zeng; Chunhai Jiao; Yanhao Xu (Journal of Plant Growth Regulation, 2023)
DNA methylation is an important epigenetic mechanism involved in gene regulation under environmental stresses in plants. However, little information is available regarding its responses to high temperature (HT) and association with HT tolerance in rice. In this study, fourteen rice genotypes were classified into the susceptible, moderate, and tolerant groups by the high temperature susceptibility index (HTSI) after HT treatment. The changes of DNA methylation in rice anthesis under normal and HT30 conditions were investigated using methylation-sensitive amplified polymorphism31 (MSAP). The MSAP results showed that the DNA methylation level significantly increased in the susceptible rice group and decreased in the tolerant rice group under HT treatment, while no significant difference was observed in the moderate rice group. More hypomethylation events were detected in the tolerant rice group, while more hypermethylation was detected in the susceptible rice group. Forty-four differentially methylated epiloci (DME) were generated under both control and HT conditions, which can clearly distinguish the susceptible, moderate, and tolerant genotypes via PCoA analysis. Approximately 43.18% of DMEs were determined to be tolerance-associated epiloci (TAEs). 63.15% TAEs were sequenced and annotated into 12 genes. Quantitative RT-PCR analysis showed that 12 TAE genes were mainly upregulated in 14 rice genotypes, and their expression levels were related to the HT tolerance of rice. Here, DEGs, generated from a number of genotypes, indicate higher probabilities for association with stress tolerance. Overall, these results suggest that DNA methylation regulation might play a key role in adaptation to HT stress in rice.

Correction to: Important revelations of different degrees of COVID‑19 lockdown on improving regional air quality: a case study of Shijiazhuang, China - Yanan Guan; Ying Shen; Xinyue Liu; Xuejiao Liu; Jing Chen; Dong Li; Man Xu; Litao Wang; Erhong Duan; Li’an Hou; Jing Han (Environmental Science and Pollution Research, 2023)

Co-occurrence network of microbial communities affected by application of anaerobic fermentation residues during phytoremediation of ionic rare earth tailings area - Liumeng Chen; Shasha Chen; Yi Zhang; Yun Long; Xiaoying Kong; Shujia Wang; Lianhua Li; Fei Wang; Yongmin Sun; An Xu (Science of The Total Environment, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Distribution and migration of antibiotic resistance genes, as well as their correlation with microbial communities in swine farm and its surrounding environments - Bin Wang; Lei Song; Wenjia Li; Li'an Hou; Jiang Li; Xiaoyi Xu; Guishang Sheng (Environmental Pollution, 2023)

Re nanoflower-decorated carbon cloth for pH-universal hydrogen evolution reaction: Unveiling the intrinsic electrocatalytic activity of metallic Re - Shiyu Xu; Peng Zhang; Hao Li; Zhengyang Li; Zongfu An; Chan-Hwa Chung; Jin Yong Lee; Ji Man Kim; Pil J. Yoo (Chemical Engineering Journal, 2023)

Correlation analysis between the occurrence of epidemic in ancient China and solar activity - Si Chen; Yong Wei; Xin’an Yue; Kaihua Xu; Mingkun Li; Wei Lin (Science China Earth Sciences, 2023)

Travertine/tufa resource conservation and sustainable development call for a world-wide initiative - Faqin Dong; Qunwei Dai; Zhongcheng Jiang; Xiaoqing Chen; Ronglin Xu; Qiang Zhang; Dejun An; Qiongfang Li; Ting Zhang; Plenkovic-Moraj Andelka; Enrico Capezzuoli; Bowen Li; et al. (Applied Geochemistry, 2023)

The prenatal weekly temperature exposure and neonatal congenital heart disease: a large population-based observational study in China - Weize Xu; Die Li; Zehua Shao; Yanqin You; Feixia Pan; Hongliang Lou; Jing Li; Yueqin Jin; Ting Wu; Lulu Pan; Jing An; Junqiu Xu; et al. (Environmental Science and Pollution Research, 2022)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

Spinal Cord Mapping of Respiratory Intercostal Motoneurons in Adult Mice - Junhong Zhang; Fenlan Luo; Shuancheng Ren; Yaling Wang; Wu Li; Kan Xu; Ziyi Zheng; Chao He; Jianxia Xia; Wei Xiong; Zhi-An Hu (Neuroscience Bulletin, 2022)

A modified TOPMODEL introducing the bedrock surface topographic index in Huangbengliu watershed, China - An-ni Qiu; Yan-jun Zhang; Gen-xu Wang; Jun Cui; Yuan-xin Song; Xiang-yang Sun; Li Chen (Journal of Mountain Science, 2022)

Application of Singularity Theory to the Distribution of Heavy Metals in Surface Sediments of the Zhongsha Islands - Yan Zhang; Shiqiao Liu; Li Zhang; Yongzhang Zhou; Jinqiang Liang; Jing’an Lu; Xiaoqiang Hu; Liang Liu; Liang Chen; Jingwei Zhang; Cheng Xu; Xinzhu Dong (Journal of Marine Science and Engineering, 2022)
This research aimed to use nonlinear theory and technology to describe the spatial distribution of heavy metals in the surface sediments of the Zhongsha Islands Sea region. The goal of this study is to explore the spatial distribution characteristics of heavy metals in the surface sediments of the Zhongsha Islands. The singularity theory and method were used to delineate heavy metal geochemical anomalies and the generalized self-similarity analysis method was used to decompose heavy metal geochemical anomalies and background concentrations. The results showed that there were abnormally high concentrations of heavy metals in the deep-sea plain area and in the western central sand trough area. The results of this study can inform priority areas for environmental monitoring. The element anomalies extracted by the singularity analysis method in this paper can be a guide to the next step in the investigation and provide the basis for the regional environmental assessment.

Important revelations of different degrees of COVID-19 lockdown on improving regional air quality: a case study of Shijiazhuang, China - Yanan Guan; Ying Shen; Xinyue Liu; Xuejiao Liu; Jing Chen; Dong Li; Man Xu; Litao Wang; Erhong Duan; Li’an Hou; Jing Han (Environmental Science and Pollution Research, 2022)

Active Depths of Main Faults in the Ying-Qiong Basin Investigated by Multi-Scale Wavelet Decomposition of Bouguer Gravity Anomalies and Power Spectral Methods - Long An; Chong Yu; Wei Gong; Deyong Li; Junhui Xing; Chong Xu; Hao Zhang (Journal of Ocean University of China, 2022)

Astrocyte-Derived TNF-α-Activated Platelets Promote Cerebral Ischemia/Reperfusion Injury by Regulating the RIP1/RIP3/AKT Signaling Pathway - Wei Li; Dengping Liu; Jiaqi Xu; Jun Zha; Chen Wang; Jianzhong An; Zhanli Xie; Shigang Qiao (Molecular Neurobiology, 2022)
Ischemic stroke is a clinical syndrome caused by the disruption of blood flow into cerebral tissues and is associated with high disability and mortality rates. Studies have established the pathological role of platelets in cerebral ischemia/reperfusion (I/R) injury, although the underlying mechanism of action remains largely unclear. In this study, we created an I/R mouse model via middle cerebral artery occlusion and reperfusion (MCAO/R) and analyzed the transcriptomic profiles of the ipsilateral and contralateral cortices using RNA-seq. We found that cerebral I/R injury induced platelet invasion and accumulation in the cerebral cortex by stimulating TNF-α secretion from activated astrocytes in the ischemic region, while TNF-α expression enhanced platelet reactivity through the RIP1/RIP3/AKT pathway. Furthermore, the inoculation of TNF-α-stimulated platelets aggravated I/R injury in mice, whereas the administration of anti-TNF-α antibodies at the onset of reperfusion alleviated ischemic damage. The RNA-seq results further showed that AP-1 transcriptionally activated TNF-α in the I/R-injured cortex by directly binding to the promoter region. These findings provide novel insights into the pathological role of platelets activated by reactive astrocyte-derived TNF-α in cerebral I/R injury.

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Basin structure and multiresource potential based on high-precision airborne gravity and magnetic data - Yan-Xu Liu; Wen-Yong Li; An-Qi Cao; Shan Gao; Ning Wang; Li-Jie Wang; Cheng Yang (Applied Geophysics, 2022)

Research Progress on Volatile Organic Compounds Emissions from Coal-fired Power Plants - Jingxin Xu; Fahua Zhu; Xinlei Ge; Haiwei Li; Xiuyong Zhao; Wenxin Tian; Xi Zhang; Yuan Bai; Fengxia An; Sheng Wang (Current Pollution Reports, 2022)

Adipose Mesenchymal Stem Cell-Derived Exosomes Promote Wound Healing Through the WNT/β-catenin Signaling Pathway in Dermal Fibroblasts - Cong Li; Yu An; Yu Sun; Fan Yang; Quanchen Xu; Zhiguo Wang (Stem Cell Reviews and Reports, 2022)
The differentiation, migration, and proliferation of skin fibroblasts are identified as key factors in cutaneous wound healing. Adipose-derived mesenchymal stem cells (ADMSCs) and their exosomes (ADMSC-Exos) have been considered as potential therapeutic tools for tissue regeneration; however, the underlying mechanisms on cutaneous wound healing are still not well understood. In this study, we successfully obtained ADMSC-Exos and found ADMSC-Exos significantly promoted the migration and proliferation of fibroblasts in a dose-dependent manner in vitro. The expression levels of COL-I and COL-III in fibroblasts treated with ADMSC-Exos were significantly increased, while the expression level of α-SMA was decreased. In addition, the enhanced protein expression of WNT2b and β-catenin confirmed the activation of the WNT/β-catenin signaling pathway and the WNT/β-catenin inhibitor (XAV939) reversed the promoting effect of ADMSC-Exos on wound healing and the β-catenin expression. Taken together, our study partially elucidates the mechanism of ADMSC-Exos in wound healing, illustrating the potential of ADMSC-Exos as a new therapeutic approach to promote skin wound healing. Graphical Abstract

Overexpression of TaLAX3-1B alters the stomatal aperture and improves the salt stress resistance of tobacco - Luhua Li; Dingli Hong; Chang An; Yuxuan Chen; Pengpeng Zhao; Xin Li; Fumin Xiong; Mingjian Ren; Ruhong Xu (Molecular Biology Reports, 2022)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

Genetic mapping of powdery mildew resistance genes in wheat landrace Guizi 1 via genotyping by sequencing - Luhua Li; Xicui Yang; Zhongni Wang; Mingjian Ren; Chang An; Susong Zhu; Ruhong Xu (Molecular Biology Reports, 2022)

Moderate intensity of static magnetic fields can alter the avoidance behavior and fat storage of Caenorhabditis elegans via serotonin - Lei Cheng; Baolin Yang; Hua Du; Tong Zhou; Yang Li; Jiajie Wu; Zhenxiao Cao; An Xu (Environmental Science and Pollution Research, 2022)

Continuous cropping of alfalfa (Medicago sativa L.) reduces bacterial diversity and simplifies cooccurrence networks in aeolian sandy soil - Yanxia Xu; Junjie Liu; Xuefeng Liu; Hong Li; Zhao Yang; Hongbao Wang; Xinyu Huang; Lan Lan; Yutong An; Lujun Li; Qin Yao; Guanghua Wang (Soil Ecology Letters, 2022)

Teleseismic P-Wave Tomography of the New Guinea-Solomon Arc System - Bing Feng; Hao Zhang; Wei Gong; Junhui Xing; Deyong Li; Chong Xu; Long An (Journal of Ocean University of China, 2022)

Targeting GATA1 and p2x7r Locus Binding in Spinal Astrocytes Suppresses Chronic Visceral Pain by Promoting DNA Demethylation - Yan-Yan Wu; Hai-Long Zhang; Xiaomin Lu; Han Du; Yong-Chang Li; Ping-An Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2022)
Irritable bowel syndrome is a gastrointestinal disorder of unknown etiology characterized by widespread, chronic abdominal pain associated with altered bowel movements. Increasing amounts of evidence indicate that injury and inflammation during the neonatal period have long-term effects on tissue structure and function in the adult that may predispose to gastrointestinal diseases. In this study we aimed to investigate how the epigenetic regulation of DNA demethylation of the p2x7r locus guided by the transcription factor GATA binding protein 1 (GATA1) in spinal astrocytes affects chronic visceral pain in adult rats with neonatal colonic inflammation (NCI). The spinal GATA1 targeting to DNA demethylation of p2x7r locus in these rats was assessed by assessing GATA1 function with luciferase assay, chromatin immunoprecipitation, patch clamp, and interference in vitro and in vivo . In addition, a decoy oligodeoxynucleotide was designed and applied to determine the influence of GATA1 on the DNA methylation of a p2x7r CpG island. We showed that NCI caused the induction of GATA1, Ten-eleven translocation 3 (TET3), and purinergic receptors (P2X7Rs) in astrocytes of the spinal dorsal horn, and demonstrated that inhibiting these molecules markedly increased the pain threshold, inhibited the activation of astrocytes, and decreased the spinal sEPSC frequency. NCI also markedly demethylated the p2x7r locus in a manner dependent on the enhancement of both a GATA1–TET3 physical interaction and GATA1 binding at the p2x7r promoter. Importantly, we showed that demethylation of the p2x7r locus (and the attendant increase in P2X7R expression) was reversed upon knockdown of GATA1 or TET3 expression, and demonstrated that a decoy oligodeoxynucleotide that selectively blocked the GATA1 binding site increased the methylation of a CpG island in the p2x7r promoter. These results demonstrate that chronic visceral pain is mediated synergistically by GATA1 and TET3 via a DNA-demethylation mechanism that controls p2x7r transcription in spinal dorsal horn astrocytes, and provide a potential therapeutic strategy by targeting GATA1 and p2x7r locus binding.

Comparison and evaluation of carrier phase PPP and single difference time transfer with multi-GNSS ambiguity resolution - Wei Xu; Wenbin Shen; Chenghui Cai; Lihong Li; Lei Wang; An Ning; Ziyu Shen (GPS Solutions, 2022)

A comparison of the reproducibility of regional precipitation properties simulated respectively by weather generators and stochastic simulation methods - Luhua Yang; Ping-an Zhong; Feilin Zhu; Yufei Ma; Han Wang; Jieyu Li; Chengjing Xu (Stochastic Environmental Research and Risk Assessment, 2022)

The association between short-term ambient air pollution and acne vulgaris outpatient visits: a hospital-based time-series analysis in Xi’an - Xiang Li; Yi Cao; Shu-Jie An; Ying Xiang; He-Xiang Huang; Bin Xu; Yao Zhang; Ya-Fei Li; Yuan-Gang Lu; Tong-Jian Cai (Environmental Science and Pollution Research, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Effect of tree form on wheat yield via changing microenvironment in almond–wheat intercropping - Wen Zhang; Hui Xie; Shou-An Han; Min Wang; Ming-Qi Pan; Xu Qiao; Long Li (Agroforestry Systems, 2022)

Bivalent Regulation and Related Mechanisms of H3K4/27/9me3 in Stem Cells - Han Sun; Yin Wang; Ying Wang; Feng Ji; An Wang; Ming Yang; Xu He; Lisha Li (Stem Cell Reviews and Reports, 2022)

Efficacy and safety of aripiprazole once-monthly versus oral aripiprazole in Chinese patients with acute schizophrenia: a multicenter, randomized, double-blind, non-inferiority study - Le Xiao; Qian Zhao; An-ning Li; Jushui Sun; Bin Wu; Lina Wang; Honggeng Zhang; Ruiling Zhang; Keqing Li; Xiaojin Xu; Tiebang Liu; Wenshun Zhang; et al. (Psychopharmacology, 2022)

Mutations in the regulatory regions result in increased streptomycin resistance and keratinase synthesis in Bacillus thuringiensis - Lei Nie; Ruijiao Zhang; Linfang Zhang; Mengyuan Ma; Congcong Li; Yi Zhang; Yafei An; Hongju Xu; Sa Xiao; Tianwen Wang (Archives of Microbiology, 2021)

Deposition records of polycyclic aromatic hydrocarbons and black carbon in peat core from Dajiuhu, Shennongjia, Central China: human activity imprint since the industrial revolution - Tianpeng Hu; Yao Mao; Weijie Liu; Mingming Shi; Cheng Cheng; An Xu; Yewang Su; Xingyu Li; Yunchao Zhang; Zhiqi Zhang; Shihua Qi; Xinli Xing (Environmental Science and Pollution Research, 2021)

A new indole alkaloid with HUVEC proliferation activities from Nauclea officinalis - Shi-Ying Mai; Yong-Hui Li; Xu-Guang Zhang; Yi-Ran Wang; Jun-Qing Zhang; An Jia (Natural Product Research, 2021)

Pathogenic Factors Identification of Brain Imaging and Gene in Late Mild Cognitive Impairment - Xia-an Bi; Lou Li; Ruihui Xu; Zhaoxu Xing (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Application of constructed wetlands in treating rural sewage from source separation with high-influent nitrogen load: a review - Xiangyu Li; Longjian Yang; Kaiqin Xu; Ke Bei; Xiangyong Zheng; Shiwen Lu; Ning An; Jinshan Zhao; Zhan Jin (World Journal of Microbiology and Biotechnology, 2021)

Parent–offspring variation transmission in full-sib families revealed predominantly paternal inheritance of chloroplast DNA in Pinus massoniana (Pinaceae) - ZhouXian Ni; PengYan Zhou; Yue Xin; Meng Xu; Li-An Xu (Tree Genetics & Genomes, 2021)

Cloud-Based Multidimensional Parallel Dynamic Programming Algorithm for a Cascade Hydropower System - Yufei Ma; Ping-an Zhong; Bin Xu; Feilin Zhu; Jieyu Li; Han Wang; Qingwen Lu (Water Resources Management, 2021)

Potential effect of EGCG on the anti-tumor efficacy of metformin in melanoma cells - An’an Xu; Jeehyun Lee; Yueling Zhao; Yuefei Wang; Xiaoli Li; Ping Xu (Journal of Zhejiang University-SCIENCE B, 2021)

The long-term effects of thinning and mixing on species and structural diversity of Chinese fir plantations - Yuanfa Li; Ji’an He; Lihua Lu; Junmo Xu; Hongxiang Wang; Shaoming Ye (New Forests, 2021)

Automatic mapping of river canyons using a digital elevation model and vector river data - Shi-Yu Xu; An-Bo Li; Tian-Tian Dong; Xian-Li Xie (Earth Science Informatics, 2021)

Phylogeography of subspecies of the sable (Martes zibellina L.) based on mitochondrial genomes: implications for evolutionary history - Bo Li; Jinyao Lu; Vladimir Monakhov; Hui Kang; Yanchun Xu; Boyang An; Muhammad Usman Ghani; Mingzhe Li; Wenwen Peng; Xingna Ma (Mammalian Biology, 2021)

Adult Stress Promotes Purinergic Signaling to Induce Visceral Pain in Rats with Neonatal Maternal Deprivation - Shufen Hu; Qian Sun; Wan-Jie Du; Jian Song; Xin Li; Ping-An Zhang; Ji-Tian Xu; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Chronic visceral pain is one of the primary symptoms of patients with irritable bowel syndrome (IBS), which affects up to 15% of the population world-wide. The detailed mechanisms of visceral pain remain largely unclear. Our previous studies have shown that neonatal maternal deprivation (NMD) followed by adult multiple stress (AMS) advances the occurrence of visceral pain, likely due to enhanced norepinephrine (NE)-β 2 adrenergic signaling. This study was designed to explore the roles of P2X3 receptors (P2X3Rs) in the chronic visceral pain induced by combined stress. Here, we showed that P2X3Rs were co-expressed in β 2 adrenergic receptor (β 2 -AR)-positive dorsal root ganglion neurons and that NE significantly enhanced ATP-induced Ca 2+ signals. NMD and AMS not only significantly increased the protein expression of P2X3Rs, but also greatly enhanced the ATP-evoked current density, number of action potentials, and intracellular Ca 2+ concentration of colon-related DRG neurons. Intrathecal injection of the P2X3R inhibitor A317491 greatly attenuated the visceral pain and the ATP-induced Ca 2+ signals in NMD and AMS rats. Furthermore, the β 2 -AR antagonist butoxamine significantly reversed the expression of P2X3Rs, the ATP-induced current density, and the number of action potentials of DRG neurons. Overall, our data demonstrate that NMD followed by AMS leads to P2X3R activation, which is most likely mediated by upregulation of β 2 adrenergic signaling in primary sensory neurons, thus contributing to visceral hypersensitivity.

Treatment Effect Analysis on Shallow Buried Bias Slope Section of Tunnel Based on Fuzzy Comprehensive Evaluation - Zhengjun Mao; Ning An; Ruting Li; Licheng Xu; Hao Wu (Geotechnical and Geological Engineering, 2020)

Effects of Sulfamethoxazole Exposure on the Growth, Antioxidant System of Chlorella vulgaris and Microcystis aeruginosa - Xiaotong Dong; Shaohua Sun; Ruibao Jia; Lirong Xu; Wei Hou; Nannan Lu; Mingquan Wang; Qinghua Zhao; Li’an Hou (Bulletin of Environmental Contamination and Toxicology, 2020)

Molecular characterization of gut microbial shift in SD rats after death for 30 days - Huan Li; E. Yang; Siruo Zhang; Jing Zhang; Lu Yuan; Ruina Liu; Shakir Ullah; Qi Wang; Nosheen Mushtaq; Yi Shi; Cuihong An; Zhenyuan Wang; et al. (Archives of Microbiology, 2020)

Genesis of the Linghu Au deposit in Xiaoqinling Region, Henan province, China: Constraints from fluid inclusions and isotope systematics - Wei Zeng; Zhi-gao Wang; Duo Wan; Feng-yue Sun; Cheng-dong Li; Reng-an Yu; Jia-ying Wang; Jian-chang Xu (Arabian Journal of Geosciences, 2020)

Segmentation of the Kepingtage thrust fault based on paleoearthquake ruptures, southwestern Tianshan, China - An Li; Yongkang Ran; Francisco Gomez; Jessica A. Thompson Jobe; Huaguo Liu; Liangxin Xu (Natural Hazards, 2020)
Decreasing deformation rates across the southern Tianshan have led to different seismogenic mechanisms and different proposed models to explain the orogen-scale fault kinematics. In this study, we focus on the segmentation of the Kepingtage fault by studying variations in the total offset and shortening rates of the Kepingtage fault along the southern front of the Tianshan. We used fault scarp mapping and trench excavations to assess fault segmentation and deformation on the Kepingtage fault. Our results indicate there are different shortening rates on the western (2.5–2.7 mm/year) versus the eastern segments (~ 0.3 mm/year), which are separated by the Piqiang tear fault. The decrease in shortening rates is not gradual; instead, it decreases sharply from west to east at the Piqiang fault. These segmentation boundaries are also supported by geodetic data and balanced structural restorations. Our data support a model where strike-slip faults accommodate step-changes in the deformation rates and the earthquake risks from west to east across the Tianshan.

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Preparation of non-sintered lightweight aggregates through co-mechanochemical treatment of oil-contaminated drill cuttings, circulation fluidized bed combustion fly ash, and quicklime - Xiaoyue Chen; Zhonghui Xu; Zhengzhen Yao; Qin Shuai; Zao Jiang; Xi Peng; Yu Li; Ran An; Xin Jiang; Han Li (Environmental Science and Pollution Research, 2020)

Antioxidant coumarin and pyrone derivatives from the insect-associated fungus Aspergillus Versicolor - Tian-Xiao Li; Dan-Dan Meng; Ying Wang; Jin-Lu An; Jia-Feng Bai; Xue-Wei Jia; Chun-Ping Xu (Natural Product Research, 2020)

A new triterpenoid saponin from Pulsatilla cernua predicted by NMR-based mosaic method - An-Dong Wang; Ying Bao; Xia Wang; Mei-Chen Li; Xu-Hong Ren; Jian-Yu Liu; Yong-Nan Xu (Natural Product Research, 2020)

Effects of carboxymethyl chitosan on the growth and nutrient uptake in Prunus davidiana seedlings - Dandi Xu; Hongyan Li; Lijin Lin; Ming’an Liao; Qunxian Deng; Jin Wang; Xiulan Lv; Honghong Deng; Dong Liang; Hui Xia (Physiology and Molecular Biology of Plants, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

Morphological characteristics and genetic diversity of Colletotrichum horii infecting persimmon tree in China - Quan-en Deng; Xiang-yang Ding; Jian-an Li; Lin-kai Cui; Jian-qiang Xu (European Journal of Plant Pathology, 2020)

Biallelic INTS1 Mutations Cause a Rare Neurodevelopmental Disorder in Two Chinese Siblings - Xuemin Zhang; Yajian Wang; Fang Yang; Jiulai Tang; Xiaoyan Xu; Li Yang; Xiu-An Yang; De Wu (Journal of Molecular Neuroscience, 2020)

Effects of parental genetic distance on offspring growth performance in Pinus massoniana: significance of parental-selection in a clonal seed orchard - ZhouXian Ni; TianDao Bai; YaBin Chen; YiFa Huang; Li-An Xu (Euphytica, 2019)

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Genetic Association Between NGFR, ADAM17 Gene Polymorphism, and Parkinson’s Disease in the Chinese Han Population - Wei-Wei Li; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Qian-Qian Shi; Jing Mei; Heng Yang; Fa-Ying Zhou; An-Yu Shi; Tao Zhang; Xiu-Qing Yao; Zhi-Qiang Xu; et al. (Neurotoxicity Research, 2019)

A facile hydrothermal method–fabricated robust and ultralight weight cellulose nanocrystal-based hydro/aerogels for metal ion removal - Xuehua Liu; Mingcong Xu; Bang An; Zhenwei Wu; Rue Yang; Chunhui Ma; Qiongtao Huang; Wei Li; Jian Li; Shouxin Liu (Environmental Science and Pollution Research, 2019)

Neurotrophin Receptor p75 mRNA Level in Peripheral Blood Cells of Patients with Alzheimer’s Disease - Yali Xu; Wei-Wei Li; Jun Wang; Chi Zhu; Ying-Ying Shen; An-Yu Shi; Gui-Hua Zeng; Zhi-Qiang Xu; Xin-Fu Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Dynamics of maize straw–derived nitrogen in soil aggregates as affected by fertilization - Yang Wang; Ming Li; Jiubo Pei; Tingting An; Muhammad Farhan Saeed; Te Shan; Yingde Xu; Jingkuan Wang (Journal of Soils and Sediments, 2019)

The sedimentary record of polycyclic aromatic hydrocarbons in Yamzho Yumco Lake: evolution of local sources and adsorption dynamic in the Tibetan Plateau - Qi Wang; Jun Li; Xu-Chuan Duan; Guo-Li Yuan; Bin Fang; An-Ting Wang (Environmental Science and Pollution Research, 2019)

The Tibetan Plateau Surface-Atmosphere Coupling System and Its Weather and Climate Effects: The Third Tibetan Plateau Atmospheric Science Experiment - Ping Zhao; Yueqing Li; Xueliang Guo; Xiangde Xu; Yimin Liu; Shihao Tang; Wenming Xiao; Chunxiang Shi; Yaoming Ma; Xing Yu; Huizhi Liu; La Jia; et al. (Journal of Meteorological Research, 2019)

Chemical and physical pretreatments of fruits and vegetables: Effects on drying characteristics and quality attributes – a comprehensive review - Li-Zhen Deng; Arun S. Mujumdar; Qian Zhang; Xu-Hai Yang; Jun Wang; Zhi-An Zheng; Zhen-Jiang Gao; Hong-Wei Xiao (Critical Reviews in Food Science and Nutrition, 2019)

Development of attenuated erythromycin‐resistant Streptococcus agalactiae vaccine for tilapia ( Oreochromis niloticus ) culture - Ling Liu; Dan‐Qi Lu; Jun Xu; Heng‐Li Luo; An‐Xing Li (Journal of Fish Diseases, 2019)
Streptococcus agalactiae is an important pathogen in fish, causing great losses of intensive tilapia farming. To develop a potential live attenuated vaccine, a re‐attenuated S. agalactiae (named TFJ‐ery) was developed from a natural low‐virulence S. agalactiae strain TFJ0901 through selection of resistance to erythromycin. The biological characteristics, virulence, stability and the immunization protective efficacy to tilapia of TFJ‐ery were determined. The results indicated that TFJ‐ery grew at a slower rate than TFJ0901. The capsule thickness of TFJ‐ery was significantly less ( p 0.05) than TFJ0901. When Nile tilapia were intraperitoneally (IP) injected with TFJ‐ery, the mortality of fish was decreased than that injected with TFJ0901. The RPS of fish immunized with TFJ‐ery at a dose of 5.0 × 10 7 CFU was 95.00%, 93.02% and 100.00% at 4, 8 and 16 weeks post‐vaccination, respectively. ELISA results showed that the vaccinated fish produced significantly higher ( p 0.05) antibody titres compared to those of control at 2 or 4 weeks post‐vaccination. Taken together, our results suggest that erythromycin could be used to attenuate S. agalactiae , and TFJ‐ery is a potent attenuated vaccine candidate to protect tilapia against S. agalactiae infections.

SNP development and diversity analysis for Ginkgo biloba based on transcriptome sequencing - Yaqiong Wu; Qi Zhou; Shujing Huang; Guibin Wang; Li-an Xu (Trees, 2019)

Variation in MERRA-2 aerosol optical depth over the Yangtze River Delta from 1980 to 2016 - Enwei Sun; Huizheng Che; Xiaofeng Xu; Zhenzhu Wang; Chunsong Lu; Ke Gui; Hujia Zhao; Yu Zheng; Yaqiang Wang; Hong Wang; Tianze Sun; Yuanxin Liang; et al. (Theoretical and Applied Climatology, 2019)

Early identification and dynamic processes of ridge-top rockslides: implications from the Su Village landslide in Suichang County, Zhejiang Province, China - Chaojun Ouyang; Wei Zhao; Huicong An; Shu Zhou; Dongpo Wang; Qiang Xu; Weile Li; Dalei Peng (Landslides, 2019)

Quantitative assessment of enterprise environmental risk mitigation in the context of Na-tech disasters - Ruru Han; Beihai Zhou; Luyang An; Haibo Jin; Lei Ma; Nan Li; Ming Xu; Linjun Li (Environmental Monitoring and Assessment, 2019)

Modeling sediment texture of river-deltaic wetlands in the Lower Barataria Bay and Lower Breton Sound, Louisiana, USA - An Li; Frank T.-C. Tsai; Kehui Xu; Jiaze Wang; Crawford M. White; Samuel J. Bentley; Qin J. Chen (Geo-Marine Letters, 2019)

Neonatal Maternal Deprivation Followed by Adult Stress Enhances Adrenergic Signaling to Advance Visceral Hypersensitivity - Wan-Jie Du; Shufen Hu; Xin Li; Ping-An Zhang; Xinghong Jiang; Shan-Ping Yu; Guang-Yin Xu (Neuroscience Bulletin, 2019)

Development and molecular cytogenetic identification of a new wheat-rye 4R chromosome disomic addition line with resistances to powdery mildew, stripe rust and sharp eyespot - Diaoguo An; Pengtao Ma; Qi Zheng; Shulan Fu; Lihui Li; Fangpu Han; Guohao Han; Jing Wang; Yunfeng Xu; Yuli Jin; Qiaoling Luo; Xiaotian Zhang (Theoretical and Applied Genetics, 2019)

Effects of long-term coastal reclamation on suitable habitat and wintering population size of the endangered Red-crowned Crane, Grus japonensis - Ning Li; Zheng Wang; Lu Xia; Feng Yan; Ling-qian Xu; Ya-jun Qiao; Xin-hai Li; Shu-qing An; Shu-bo Fang (Hydrobiologia, 2019)

Virulence regulation of cel‐ EIIB protein mediated PTS system in Streptococcus agalactiae in Nile tilapia - Jun Xu; Yun‐Dan Xie; Ling Liu; Song Guo; You‐Lu Su; An‐Xing Li (Journal of Fish Diseases, 2019)
Streptococcus agalactiae is a major pathogen of tilapia causing significant economic losses for the global aquatic industry yearly. To elucidate the role of cel‐ EIIB protein‐mediated phosphotransferase systems ( PTS ) in the virulence regulation of S. agalactiae , cel‐ EIIB gene deletion in a virulent strain THN 0901 was achieved by homologous recombination. The cellobiose utilization of △ cel‐ EIIB strain was significantly decreased relative to S.a . THN 0901 strain incubating in LB with 10 mg/ ml cellobiose ( p cel‐ EIIB strain was also significantly decreased when cultured in BHI medium ( p cel‐ EIIB strain was dramatically decreased (20%), of which S.a . THN 0901 strain and △ cel‐ EIIB ::i strain were 53.33% and 50%, respectively. The competition experience using tilapia model indicated the invasion and colonization ability of △ cel‐ EIIB strain was significantly weaker than that of S.a . THN 0901 strain ( p cel‐ EIIB ::i strain, the mRNA expression of csrS , csrR , rgfA, rgfC, bgrR and bgrS was significantly downregulated in △ cel‐ EIIB strain ( p EIIB protein‐mediated cel‐ PTS not only contributes to biofilm formation and virulence regulation, but also plays an important role in the invasion and colonization of S. agalactiae .

Hippocampal proBDNF facilitates place learning strategy associated with neural activity in rats - Lei An; Xiaoliang Li; Chunzhi Tang; Nenggui Xu; Wei Sun (Brain Structure and Function, 2018)

Development and characterization of chloroplast microsatellite markers for Pinus massoniana and their application in Pinus (Pinaceae) species - Zhouxian Ni; Pengyan Zhou; Meng Xu; Li-An Xu (Journal of Genetics, 2018)

Effects of dietary myo-inositol on growth, chemical composition and plasma chemistry of Amur sturgeon Acipenser schrenckii - Chang’an Wang; Hongbai Liu; Jinnan Li; Liansheng Wang; Zhigang Zhao; Liang Luo; Qiyou Xu (Aquaculture International, 2018)

N-(3-oxo-acyl) homoserine lactone induced germ cell apoptosis and suppressed the over-activated RAS/MAPK tumorigenesis via mitochondrial-dependent ROS in C. elegans - Bin Chen; Xianbin Cao; Huayi Lu; Pengbo Wen; Xiaojing Qi; Shaopeng Chen; Lijun Wu; Chi Li; An Xu; Guoping Zhao (Apoptosis, 2018)

Frond transformation system mediated by Agrobacterium tumefaciens for Lemna minor - Gui-Li Yang; Yang Fang; Ya-Liang Xu; Li Tan; Qi Li; Yang Liu; Fan Lai; Yan-Ling Jin; An-Ping Du; Kai-Ze He; Xin-Rong Ma; Hai Zhao (Plant Molecular Biology, 2018)

Effects of organic carbon addition on water quality and growth performance of bottom- and filter-feeding carp in a minimum-water-exchange pond polyculture system - Zhigang Zhao; Liang Luo; Chang’an Wang; Jinnan Li; Liansheng Wang; Xue Du; Qiyou Xu (Fisheries Science, 2018)

Identification of toxic substances in phenol-acetone wastewater on activated sludge and selective toxicity removal performance with ferrous pretreatment - Lulu Wang; Qianqian Lv; Mingdong An; Zhongyi Liu; Yudong Song; Yuexi Zhou; Jie Li; Jixian Xu (Environmental Science and Pollution Research, 2018)

Early Carboniferous ophiolite in central Qiangtang, northern Tibet: record of an oceanic back-arc system in the Palaeo-Tethys Ocean - Tian-Yu Zhang; Jian-Jun Fan; Cai Li; Chao-Ming Xie; Ming Wang; Yan-Wang Wu; Meng-Jing Xu; Wei Xu; Jin-Heng Liu; An-Bo Luo (International Geology Review, 2018)

Climatology of cloud-base height from long-term radiosonde measurements in China - Yong Zhang; Lejian Zhang; Jianping Guo; Jinming Feng; Lijuan Cao; Yang Wang; Qing Zhou; Liangxu Li; Bai Li; Hui Xu; Lin Liu; Ning An; et al. (Advances in Atmospheric Sciences, 2018)

AgNO3 prevents the occurrence of hyperhydricity in Dianthus chinensis L. by enhancing water loss and antioxidant capacity - Hongyang Gao; Pinsan Xu; Jiawei Li; Huining Ji; Lijia An; Xiuying Xia (In Vitro Cellular & Developmental Biology - Plant, 2017)

Effects of dietary phosphorus on growth, body composition, and blood chemistry of juvenile taimen Hucho taimen - Chang’an Wang; Liansheng Wang; Jinnan Li; Dongli Qin; Zhigang Zhao; Liang Luo; Xue Du; Qiyou Xu; Jiasheng Yin (Aquaculture International, 2017)

Genetic parameters for growth traits and stem-straightness in Eucalyptus urophylla × E. camaldulensis hybrids from a reciprocal mating design - Ying’an Zhu; ShiJun Wu; Jianmin Xu; Zhaohua Lu; Guangyou Li; Yang Hu; Xueyan Yang; David Bush (Euphytica, 2017)

Experimental and Numerical Investigation of Permeability Evolution with Damage of Sandstone Under Triaxial Compression - Xu Chen; Jin Yu; Chun’an Tang; Hong Li; Shanyong Wang (Rock Mechanics and Rock Engineering, 2017)

Effects of the supplementation of vitamin D3 on the growth and vitamin D metabolites in juvenile Siberian sturgeon (Acipenser baerii) - Liansheng Wang; Hong Xu; Yang Wang; Chang’an Wang; Jinnan Li; Zhigang Zhao; Liang Luo; Xue Du; Qiyou Xu (Fish Physiology and Biochemistry, 2017)

Anti-TGFβ-1 receptor inhibitor mediates the efficacy of the human umbilical cord mesenchymal stem cells against liver fibrosis through TGFβ-1/Smad pathway - Ji Xuan; Wang Feng; Zheng-tao An; Jian Yang; Hua-bing Xu; Jing Li; Zhi-fei Zhao; Wei Wen (Molecular and Cellular Biochemistry, 2017)

Differentially expressed gene analysis of Tamarix chinensis provides insights into NaCl-stress response - Jianwen Wang; Meng Xu; Yincong Gu; Li-an Xu (Trees, 2017)

Functional identification of apple MdJAZ2 in Arabidopsis with reduced JA-sensitivity and increased stress tolerance - Xiu-Hong An; Yu-Jin Hao; En-Mao Li; Kai Xu; Cun-Gang Cheng (Plant Cell Reports, 2017)

Two comparative approaches to identify the conservation priority areas impacted by heavy metals on Yellow Sea coasts - Ning Li; Wen Yang; Lingqian Xu; Xiaobo Jia; Shuqing An; Shubo Fang (Journal of Coastal Conservation, 2017)

Effects of tank colour on growth and survival of taimen Hucho taimen (Pallas, 1773) larvae - Chang’an Wang; Qiyou Xu; Jinnan Li; Liansheng Wang; Zhigang Zhao; Xue Du; Liang Luo; Jiasheng Yin (Aquaculture International, 2017)

Microscale chemical features of sediment-water interface in Hongfeng Lake - Jingfu Wang; Jing’an Chen; Zhihui Dai; Jian Li; Yang Xu; Jing Luo (Journal of Earth Science, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Selenium Deficiency Affects the mRNA Expression of Inflammatory Factors and Selenoprotein Genes in the Kidneys of Broiler Chicks - Jiu-li Zhang; Bo Xu; Xiao-dan Huang; Yu-hong Gao; Yu Chen; An-shan Shan (Biological Trace Element Research, 2016)

Neoarchaean quartz diorites in the Jiefangyingzi area, Central Asian Orogenic Belt: geological and tectonic significance - Xing-An Wang; Shi-Chao Li; Zhong-Yuan Xu; Kai Zhu (International Geology Review, 2016)

Construction and evaluation of nitric oxide generating vascular graft material loaded with organoselenium catalyst via layer-by-layer self-assembly - Jun An; SiYuan Chen; JingChen Gao; Xu Zhang; YuanYuan Wang; YanDong Li; Sergey Mikhalovsky; DeLing Kong; ShuFang Wang (Science China Life Sciences, 2015)
A new biomimetic material for artificial blood vessel with in situ catalytic generation of nitric oxide (NO) was prepared in this study. Organoselenium immobilized polyethyleneimine as NO donor catalyst and sodium alginate were alternately loaded onto the surface of electrospun polycaprolactone matrix via electrostatic layer-by-layer self-assembly. This material revealed significant NO generation when contacting NO donor S-nitrosoglutathione (GSNO). Adhesion and spreading of smooth muscle cells were inhibited on this material in the presence of GSNO, while proliferation of endothelial cells was promoted. In vitro platelet adhesion and arteriovenous shunt experiments demonstrated good antithrombotic properties of this material, with inhibited platelet activation and aggregation, and prevention of acute thrombosis. This study may provide a new method of improving cellular function and antithrombotic property of vascular grafts.

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

Molecular mapping of a new powdery mildew resistance gene Pm2b in Chinese breeding line KM2939 - Pengtao Ma; Hongxing Xu; Yunfeng Xu; Lihui Li; Yanmin Qie; Qiaoling Luo; Xiaotian Zhang; Xiuquan Li; Yilin Zhou; Diaoguo An (Theoretical and Applied Genetics, 2015)

A theoretical analysis of basin-scale groundwater temperature distribution - Ran An; Xiao-Wei Jiang; Jun-Zhi Wang; Li Wan; Xu-Sheng Wang; Hailong Li (Hydrogeology Journal, 2015)

Genome-Wide Analysis of the C3H Zinc Finger Transcription Factor Family and Drought Responses of Members in Aegilops tauschii - An-Long Jiang; Zhao-Shi Xu; Guang-Yao Zhao; Xiao-Yu Cui; Ming Chen; Lian-Cheng Li; You-Zhi Ma (Plant Molecular Biology Reporter, 2014)

Spatial distribution characteristics of surface tidal currents in the southwest of Taiwan Strait - Zhiben Shen; Xiongbin Wu; Hang Lin; Xiaofeng Chen; Xing’an Xu; Lun Li (Journal of Ocean University of China, 2014)

Characterization of the morphology and genome of an Escherichia coli podovirus - Yuhui Hua; Xiaoping An; Guangqian Pei; Shasha Li; Wei Wang; Xiaomeng Xu; Huahao Fan; Yong Huang; Zhiyi Zhang; Zhiqiang Mi; Jiankui Chen; Jingyun Li; et al. (Archives of Virology, 2014)

Inheritance and genetic mapping of a gene for seedling resistance to powdery mildew in wheat line X3986-2 - Pengtao Ma; Hongxing Xu; Qiaoling Luo; Yanmin Qie; Yilin Zhou; Yunfeng Xu; Haiming Han; Lihui Li; Diaoguo An (Euphytica, 2014)

Posterior Trochanteric Osteotomy in Acetabular Fractures for 32 Cases - Yunfei Niu; Xiaofei An; Shuogui Xu; Dajiang Wu; Chuncai Zhang; Ming Li (Cell Biochemistry and Biophysics, 2014)

Phylogeography and evolution of a fungal–insect association on the T ibetan P lateau - Yongjie Zhang; Shu Zhang; Yuling Li; Shaoli Ma; Chengshu Wang; Meichun Xiang; Xin Liu; Zhiqiang An; Jianping Xu; Xingzhong Liu (Molecular Ecology, 2014)
Parasitoidism refers to a major form of interspecies interactions where parasitoids sterilize and/or kill their hosts typically before hosts reach reproductive age. However, relatively little is known about the evolutionary dynamics of parasitoidism. Here, we investigate the spatial patterns of genetic variation of Chinese cordyceps, including both the parasitoidal fungus Ophiocordyceps sinensis and its host insects. We sampled broadly from alpine regions on the Tibetan Plateau and obtained sequences on seven fungal and three insect DNA fragments from each of the 125 samples. Seven and five divergent lineages/cryptic species were identified within the fungus and host insects, respectively. Our analyses suggested that O . sinensis and host insects originated at similar geographic regions in southern Tibet/Yunnan, followed by range expansion to their current distributions. Cophylogenetic analyses revealed a complex evolutionary relationship between O. sinensis and its host insects. Significant congruence was found between host and parasite phylogenies and the time estimates of divergence were similar, raising the possibility of the occurrence of cospeciation events, but the incongruences suggested that host shifts were also prevalent. Interestingly, one fungal genotype was broadly distributed, consistent with recent gene flow. In contrast, the high‐frequency insect genotypes showed limited geographic distributions. The dominant genotypes from both the fungus and the insect hosts may represent ideal materials from which to develop artificial cultivation of this important Chinese traditional medicine. Our results demonstrate that both historical and contemporary events have played important roles in the phylogeography and evolution of the O. sinensis –ghost moth parasitoidism on the Tibetan Plateau.

Evaluation of geographic distribution of high-molecular-weight glutenin subunits (HMW-GS) in wild and cultivated Triticum species - Wei Li; Yu-Ming Wei; Li-Li Xu; An-Jun Liu; Yu-Zhen Sheng; Zhi-En Pu; Guo-Yue Cheng; You-Liang Zheng (Genetic Resources and Crop Evolution, 2014)

Development and validation of molecular markers closely linked to the wheat stripe rust resistance gene YrC591 for marker-assisted selection - Hongxing Xu; Jie Zhang; Ping Zhang; Yanmin Qie; Yongchun Niu; Hongjie Li; Pengtao Ma; Yunfeng Xu; Diaoguo An (Euphytica, 2014)

A Magnetic Nanoparticle Stabilized Gas Containing Emulsion for Multimodal Imaging and Triggered Drug Release - Wei Guo; Diancheng Li; Jia-an Zhu; Xiaohui Wei; Weiwei Men; Dazhi Yin; Mingxia Fan; Yuhong Xu (Pharmaceutical Research, 2014)

Oxidative Stress and Autophagic Alteration in Brainstem of SOD1-G93A Mouse Model of ALS - Ting An; Pengxiao Shi; Weisong Duan; Shipan Zhang; Pin Yuan; Zhongyao Li; Dongxia Wu; Zuoshang Xu; Chunyan Li; Yansu Guo (Molecular Neurobiology, 2014)

Identification and characterization of three PeSHRs and one PeSCR involved in adventitious root development of Populus - Lei Xuan; Meng Xu; Caihui Chen; Chunxia Yang; Li’an Xu; Minren Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Characterization of masson pine (Pinus massoniana Lamb.) microsatellite DNA by 454 genome shotgun sequencing - Tian-Dao Bai; Li-An Xu; Meng Xu; Zhang-Rong Wang (Tree Genetics & Genomes, 2014)

Effects of Dietary Selenium Deficiency or Excess on Gene Expression of Selenoprotein N in Chicken Muscle Tissues - Jiu-li Zhang; Zi-Wei Zhang; An-Shan Shan; Shi-wen Xu (Biological Trace Element Research, 2014)

Response simulation and theoretical calibration of a dual-induction resistivity LWD tool - Wei Xu; Shi-Zhen Ke; An-Zong Li; Peng Chen; Jun Zhu; Wei Zhang (Applied Geophysics, 2014)

Frost-free season lengthening and its potential cause in the Tibetan Plateau from 1960 to 2010 - Dan Zhang; Wenhui Xu; Jiayun Li; Zhe Cai; Di An (Theoretical and Applied Climatology, 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

Microbial and enzymatic properties in response to amelioration of an acidic Ultisol by industrial and agricultural by-products - Jiu Yu Li; Zhao Dong Liu; An Zhen Zhao; Ren Kou Xu (Journal of Soils and Sediments, 2014)

Mapping QTLs for yield and nitrogen-related traits in wheat: influence of nitrogen and phosphorus fertilization on QTL expression - Yunfeng Xu; Ruifang Wang; Yiping Tong; Huatian Zhao; Qingen Xie; Dongcheng Liu; Aimin Zhang; Bin Li; Hongxing Xu; Diaoguo An (Theoretical and Applied Genetics, 2014)

A Murine Model of Hepatic Veno-occlusive Disease Induced by Allogeneic Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Licai An; Ting Fang; Bin Pan; Haiying Sun; Chong Chen; Jiang Cao; Zhenyu Li; Kailin Xu (Cell Biochemistry and Biophysics, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

An exploratory analysis of benthic macroinvertebrates as indicators of the ecological status of the Upper Yellow and Yangtze Rivers - Baozhu Pan; Zhaoyin Wang; Zhiwei Li; Guo-an Yu; Mengzhen Xu; Na Zhao; Gary Brierley (Journal of Geographical Sciences, 2013)

Paleoseismic study of the east Kalpintage fault in southwest Tianshan based on deformation of alluvial fans and 10Be dating - An Li; Yongkang Ran; Liangxin Xu; Huaguo Liu (Natural Hazards, 2013)

Molecular cytogenetic characterization of a new wheat–rye 4R chromosome translocation line resistant to powdery mildew - Diaoguo An; Qi Zheng; Yilin Zhou; Pengtao Ma; Zhenling Lv; Lihui Li; Bin Li; Qiaoling Luo; Hongxing Xu; Yunfeng Xu (Chromosome Research, 2013)

The Very Large G Protein Coupled Receptor (Vlgr1) in Hair Cells - Jin-Peng Sun; Rong Li; Hong-Ze Ren; An-Ting Xu; Xiao Yu; Zhi-Gang Xu (Journal of Molecular Neuroscience, 2013)

Paracoccus siganidrum sp. nov., isolated from fish gastrointestinal tract - Ying Liu; Qing-yi Xie; Kui Hong; Lei Li; Ya-mei Zhao; Yi-li Tang; Jun-ying An; Ping-ping Zhu; Chun-hou Xu (Antonie van Leeuwenhoek, 2013)

Finer resolution observation and monitoring of global land cover: first mapping results with Landsat TM and ETM+ data - Peng Gong; Jie Wang; Le Yu; Yongchao Zhao; Yuanyuan Zhao; Lu Liang; Zhenguo Niu; Xiaomeng Huang; Haohuan Fu; Shuang Liu; Congcong Li; Xueyan Li; et al. (International Journal of Remote Sensing, 2013)

Genetic diversity and population structure in wild Sichuan rhesus macaques - Di Yan Li; Huai Liang Xu; Jessica Satkoski Trask; Qing Zhu; An Chun Cheng; David Glenn Smith; Debbie George; Long Zhang (Molecular Biology Reports, 2013)

Genomewide analysis of the chitinase gene family in Populus trichocarpa - CONG JIANG; RUI FANG HUANG; JIA LIANG SONG; MIN REN HUANG; LI AN XU (Journal of Genetics, 2013)

Recurrence of paleoearthquakes on the southeastern segment of the Ganzi-Yushu Fault, central Tibetan Plateau - An Li; Feng Shi; XiaoPing Yang; XiWei Xu (Science China Earth Sciences, 2013)

A simple method to prepare magnetic modified beer yeast and its application for cationic dye adsorption - Jun-Xia Yu; Li-Yan Wang; Ru-An Chi; Yue-Fei Zhang; Zhi-Gao Xu; Jia Guo (Environmental Science and Pollution Research, 2013)

Development of a substrate-coupled biocatalytic process driven by an NADPH-dependent sorbose reductase from Candida albicans for the asymmetric reduction of ethyl 4-chloro-3-oxobutanoate - Ping Cai; Mingdong An; Lin Xu; Sheng Xu; Ning Hao; Yan Li; Kai Guo; Ming Yan (Biotechnology Letters, 2012)

Isolation and characterization of a Chinese strain of human enterovirus 74 from a healthy child in the Tibet Autonomous Region of China - Jitao Wang; Yong Zhang; Mei Hong; Xiaolei Li; Shuangli Zhu; Dongmei Yan; Dongyan Wang; Hongqiu An; Tsewang; Jianrong Han; Wenbo Xu (Archives of Virology, 2012)

Mapping QTLs with epistatic effects and QTL × treatment interactions for salt tolerance at seedling stage of wheat - Yun-Feng Xu; Diao-Guo An; Dong-Cheng Liu; Ai-Min Zhang; Hong-Xing Xu; Bin Li (Euphytica, 2012)

Genetic transformation of wheat: current status and future prospects - Jiarui Li; Xingguo Ye; Baoyan An; Lipu Du; Huijun Xu (Plant Biotechnology Reports, 2012)

QTL mapping for seedling traits in wheat grown under varying concentrations of N, P and K nutrients - Ying Guo; Fan-mei Kong; Yun-feng Xu; Yan Zhao; Xue Liang; Ying-ying Wang; Diao-guo An; Si-shen Li (Theoretical and Applied Genetics, 2012)

Rupture segmentation and slip partitioning of the mid-eastern part of the Kunlun Fault, north Tibetan Plateau - ChenXia Li; XiWei Xu; XueZe Wen; RongZhang Zheng; GuiHua Chen; Hu Yang; YanFen An; Xiang Gao (Science China Earth Sciences, 2011)

High-mobility group A1 proteins enhance the expression of the oncogenic miR-222 in lung cancer cells - Yunzhi Zhang; Teng Ma; Shuping Yang; Mingying Xia; Jing Xu; Haijia An; Yajun Yang; Shilin Li (Molecular and Cellular Biochemistry, 2011)

Precise mapping Fhb5, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Mingzhi Tang; Yan Zhou; Guoqiang Li; Xia An; Feng Lin; Haibin Xu; Haiyan Jia; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2011)

The combined positive effects of two dominant species in an arid shrub-herbaceous community: implications from the performance of two associate species - Ming-Juan Zhang; Maosong Liu; Yutong Li; Chi Xu; Shuqing An (Plant Ecology, 2011)

Integrating miRNA and mRNA expression profiles in response to heat stress-induced injury in rat small intestine - Jin Yu; Fenghua Liu; Peng Yin; Xiaoyu Zhu; Guiling Cheng; Nin Wang; An Lu; Weili Luan; Nuowei Zhang; Jiefeng Li; Kaijun Guo; Yulong Yin; et al. (Functional & Integrative Genomics, 2011)

Viral distribution and lesions in Kunming mice experimentally infected with porcine circovirus type 2b - Zhi-Bang Deng; Nai-Dong Wang; Dao-Jun Xu; An-Wen Yuan; Meng Ge; Wei Luo; Li-Qun Xue; Xing-Long Yu (Veterinary Research Communications, 2011)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)

Molecular Characterisation of the Faecal Microbiota in Patients with Type II Diabetes - Xiaokang Wu; Chaofeng Ma; Lei Han; Muhammad Nawaz; Fei Gao; Xuyan Zhang; Pengbo Yu; Chang’an Zhao; Lianchuan Li; Aiping Zhou; Juan Wang; John E. Moore; et al. (Current Microbiology, 2010)

Fine mapping Fhb4, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Guoqiang Li; Haiyan Jia; Feng Xu; Feng Lin; Mingzhi Tang; Yao Wang; Xia An; Haibin Xu; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

A genetic linkage map of Populus adenopoda Maxim. × P. alba L. hybrid based on SSR and SRAP markers - Yuanxiu Wang; Xiaoyan Sun; Biyue Tan; Bo Zhang; Li-an Xu; Minren Huang; Mingxiu Wang (Euphytica, 2010)

Effect of dietary protein reduction with synthetic amino acids supplementation on growth performance, digestibility, and body composition of juvenile Pacific white shrimp, Litopenaeus vannamei - Ming-Yan Huai; Yong-Jian Liu; Li-Xia Tian; Shi-Xi Deng; An-Long Xu; Wen Gao; Hui-Jun Yang (Aquaculture International, 2010)

Adsorption and desorption of Cu(II) and Cd(II) in the tropical soils during pedogenesis in the basalt from Hainan, China - Kai Zhong; Ren-kou Xu; An-zhen Zhao; Jun Jiang; Diwakar Tiwari; Hang Li (Carbonates and Evaporites, 2010)

Forest ecosystem services and their values in Beijing - Gaodi Xie; Wenhua Li; Yu Xiao; Biao Zhang; Chunxia Lu; Kai An; Jixing Wang; Kang Xu; Jinzeng Wang (Chinese Geographical Science, 2010)

A Sabin 2-related poliovirus recombinant contains a homologous sequence of human enterovirus species C in the viral polymerase coding region - Yong Zhang; Fan Zhang; Shuangli Zhu; Li Chen; Dongmei Yan; Dongyan Wang; Ruiyan Tang; Hui Zhu; Xiaohui Hou; Hongqiu An; Hong Zhang; Wenbo Xu (Archives of Virology, 2010)

Molecular cloning, functional analysis and localization of a novel gene encoding polygalacturonase-inhibiting protein in Chorispora bungeana - Cuixia Di; Ming Li; Feng Long; Muqun Bai; Yajie liu; Xiaolin Zheng; Shijian Xu; Yun Xiang; Zhenglong Sun; Lizhe An (Planta, 2009)

Mediators, Genes and Signaling in Adventitious Rooting - Shi-Weng Li; Lingui Xue; Shijian Xu; Huyuan Feng; Lizhe An (The Botanical Review, 2009)

Passive Protection Assay of Monoclonal Antibodies Against Dengue Virus in Suckling Mice - Zongtao Chen; Li-Mei Liu; Na Gao; Xiao-Feng Xu; Jun-Lei Zhang; Jia-Li Wang; Jing An (Current Microbiology, 2009)

Analysis of VOC emissions using PCA/APCS receptor model at city of Shanghai, China - Fuhai Geng; Changjie Cai; Xuexi Tie; Qiong Yu; Junlin An; Li Peng; GuangQiang Zhou; Jianming Xu (Journal of Atmospheric Chemistry, 2009)

Study of Antibacterial Activity of ZnZnbisporphyrin Complexes and its Free Components on Staphylococcus aureus by Microcalorimetry - Xiang-jiao Xu; Chun-qiao Chen; Zhuo-yuan Wang; Yi Zhang; An-xin Hou; Chao-Hong Li; Yi Liu (Biological Trace Element Research, 2009)

Contrasting chemical and isotopic compositions of organic matter in Changjiang (Yangtze River) estuarine and East China Sea shelf sediments - Xu-Chen Wang; Ming-Yi Sun; An-Chun Li (Journal of Oceanography, 2008)

Nitric Oxide Alleviates Oxidative Damage Induced by Enhanced Ultraviolet-B Radiation in Cyanobacterium - Lingui Xue; Shiweng Li; Hongmei Sheng; Huyuan Feng; Shijian Xu; Lizhe An (Current Microbiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

Evaluation of caspase-dependent apoptosis during fluoride-induced liver lesion in pigs - Xiu An Zhan; Min Wang; Zi Rong Xu; Wei Fen Li; Jian Xin Li (Archives of Toxicology, 2006)

The impact of NiO on microstructure and electrical property of solid oxide fuel cell anode - Yan Li; Zhong-yang Luo; Chun-jiang Yu; Dan Luo; Zhu-an Xu; Ke-fa Cen (Journal of Zhejiang University-SCIENCE B, 2005)

Land cover changes in the rural-urban interaction of Xi’an region using Landsat TM/ETM data - Jiang Jianjun; Zhou Jie; Wu Hong’an; Ai Li; Zhang Hailong; Zhang Li; Xu Jun (Journal of Geographical Sciences, 2005)

Chemical Modification of Insulin by N-phosphorylation - Yan Liu; Peng-xiang Xu; Jian-bo Hou; Li-feng Yang; Jin-an Chen; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2005)

Bacterial diversity in malan ice core from the Tibetan Plateau - S. R. Xiang; T. D. Yao; L. Z. An; B. Q. Xu; Z. Li; G. J. Wu; Y. Q. Wang; S. Ma; X. R. Chen (Folia Microbiologica, 2004)

High-level expression of a soluble snake venom enzyme, gloshedobin, in E. coli in the presence of metal ions - Qing Yang; Jianqiang Xu; Min Li; Xuyu Lei; Lijia An (Biotechnology Letters, 2003)

Expression of gloshedobin, a thrombin-like enzyme from the venom of Gloydius shedaoensis, in Escherichia coli - Qing Yang; Min Li; Jianqiang Xu; Yongming Bao; Xuyu Lei; Lijia An (Biotechnology Letters, 2003)

Cloning and expression of defibrase cDNA from the venom of Gloydius shedaoensis * * - Qing Yang; Xiaoming Xu; Min Li; Xiaodong Yuan; Zhiguo Su; Jan-Christer Janson; Lijia An (Biotechnology Letters, 2002)